Nicotine formulations
Loading nicotine through solid porous chemical bonded ceramic system solves the problems of unstable release and safety of existing nicotine products, achieves continuous release and stable storage, and improves the safety and convenience of use of the product.
Patent Information
- Application Number
- CN202380036184.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-15
- Filing Date
- 2023-04-03
- Publication Date
- 2024-12-27
AI Technical Summary
Existing nicotine delivery products release a large amount of nicotine in a short period of time, resulting in unstable release curves and safety hazards, and it is difficult to control the storage and release of nicotine, affecting its durability and safety in oral use.
Using a solid porous chemical bonded ceramic system, nicotine or its salt is loaded into the pores of the ceramic system. By controlling the pore size and porosity of the ceramic, the continuous release and stable storage of nicotine are achieved, avoiding evaporation losses, and with pH regulators Combined to optimize release rate.
It achieves the continuous and stable release of nicotine, extends the shelf life of the product, improves safety and convenience of use, and ensures the effective delivery of nicotine and a lasting flavor experience.
Smart Images

Figure CN119212682A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a new powdered product capable of storing and releasing nicotine. The present invention also relates to the use of a nicotine-containing powder in the oral delivery of nicotine. The powder can be used to help quit smoking, treat nicotine dependence or alleviate the symptoms of nicotine dependence. The powder can also be used in products for recreational use. Background Art
[0002] A variety of nicotine replacement therapy products are commercially available, including patches, gum, lozenges, nicotine pouches, sublingual tablets, inhalers, and nasal sprays (U. Wadgave et al., Int J Health Sci (Qassim), 2016 Jul;10(3):425–435). Nicotine replacement therapies such as these can be used to help tobacco users overcome difficulties caused by nicotine withdrawal when trying to reduce their exposure to tobacco products, particularly cigarettes.
[0003] Some nicotine delivery systems are also used by individuals to provide a pleasurable sensation resulting from nicotine ingestion. Intraoral products used in this manner include nicotine pouches and snus, the latter being particularly popular in Norway and Sweden. Snus is a product containing tobacco, typically provided in the form of loose snus or portioned snus. Snus products are also a convenient and safer alternative to cigarettes, as they provide a source of nicotine without exposing users to some of the risks associated with smoking, such as harmful substances found in cigarette smoke (e.g., carbon monoxide, benzene, and formaldehyde) and harmful substances found in cigarettes themselves (e.g., vinyl chloride used in cigarette filters).
[0004] Loose snuff is a slightly moist powder that can be dispensed with the fingertips or a specially made device and packaged into cylindrical or spherical shapes. The shaped snuff block is then placed under their upper lip. Over time, the demand for loose snuff has been replaced by portioned varieties, which benefit users due to their easy handling and more discreet nature.
[0005] Snus is packaged as a slightly moist powder in a small tea bag-like pouch that can also be placed under the upper lip. Like snus, snus is typically held in the mouth for a period of between five minutes and one hour, and nicotine is released throughout this period.
[0006] Snus portions come in three different sizes: mini, regular / large (most common), and extra large. Mini portions typically weigh close to 0.5g, regular (large) portions weigh around 0.8g to 1g, and extra large portions can weigh up to 1.7g. Some manufacturers also offer the option of "regular" and "long" versions of the regular-sized pouches, with their contents weighing similarly. These long portions differ from traditional pouches in that they are thinner but longer to fit more comfortably against the gums. Snus products containing tobacco typically require refrigerated storage conditions, primarily to slow the drying of the tobacco. Nicotine pouches that do not contain tobacco are also typically refrigerated to improve product stability.
[0007] Nicotine pouches are white, pre-portioned pouches containing tobacco-derived or synthetic nicotine, possibly in salt form, but without tobacco leaves, ground tobacco (i.e. dust), or tobacco stems. They are described as being similar to snus, or a tobacco-free version of snus. Non-tobacco-based nicotine pouches are commercially available, and one of the first examples of this is the A Swedish Labeled products (N. Plurphanswat et al., The American Journal on Addictions, 29: 279–286, 2020; Lunell E. et al., Nicotine & Tobacco Research, 2020, 1757–1763). Many commercial products containing cellulose that deliver nicotine are available. However, when placed in the mouth, cellulose can interact with water to form a sticky mass in the consumer's mouth, which can have a negative impact on the user's flavor experience and therefore may affect the release of nicotine.
[0008] Nicotine pouches have been approved by, for example, the Norwegian Medicines Agency for smoking cessation and are sold as nicotine replacement therapy. Nicotine pouches are also increasingly used recreationally as a substitute for tobacco products such as cigarettes and snuff. Nicotine pouches can be dry or slightly moist. Slightly moist pouches generally feel more comfortable in the mouth and generally provide a faster release of nicotine. Slightly moist pouches generally contain glycerine.
[0009] To use a nicotine pouch, the user places the pouch in contact with the inner surface of the oral cavity, typically between the upper lip and gums, behind the lower lip or against the cheek, and holds it there as the nicotine and flavor are released, much like a portion of snus. The pouch is typically held in the mouth for a period of five minutes to one hour, and then discarded when used up.
[0010] A fast-release oral nicotine product is disclosed in an international patent application with publication number WO 2019 / 110073. A pouch containing nicotine in free salt form is disclosed in U.S. Pat. No. 9,161,908.
[0011] By increasing the pH of the oral environment above normal levels, generally to around pH 8-9, the delivery of nicotine through the oral mucosa (particularly the sublingual and buccal mucosa) can be greatly enhanced (see Ciolino LA, McCauley HA, Fraser DB, Wolnik KA. J. Anal. Toxicol. 2001; 25: 15–25 and Tomar SL et al. Tobacco Control 1997; 6: 219-225). pH regulators or suitable buffers can be incorporated into oral formulations to achieve this pH increase.
[0012] Commercially available nicotine pouches typically have a release profile in which a large portion of the nicotine is released in a short period of time, and may cause the nicotine to be swallowed and / or cause mucosal saturation. It is presumed that if the mucosa and surrounding saliva are saturated, this will cause a large amount of available nicotine to be washed away by saliva and swallowed. Controlling the total amount and rate of nicotine released from oral preparations to provide lasting therapeutic and / or non-therapeutic effects, and ensuring that the product has a commercially useful shelf life, presents further challenges. Due to the toxicity of nicotine itself, the manufacture of nicotine-containing products also brings safety challenges. The demand for oral permucosal products (oral products) that provide controlled release of nicotine and also provide and maintain a suitable alkaline environment to ensure that nicotine is fully taken into the bloodstream has not yet been met.
[0013] Furthermore, there is an unmet need for products that provide a lasting flavor while remaining in the mouth for an extended period of time.
[0014] We have now designed a novel powder containing nicotine or a salt thereof which has advantageous properties and which solves one or more problems associated with current nicotine formulations intended for intraoral delivery.
[0015] The listing or discussion of an apparently prior-published document in this specification is not necessarily considered an admission that the document is prior art or part of the common general knowledge. Summary of the invention
[0016] According to a first aspect of the present invention, there is provided a powder comprising a solid porous chemically bonded ceramic system and nicotine or a salt thereof, wherein the nicotine or a salt thereof is located within the pores of the chemically bonded ceramic system.
[0017] These powders are referred to hereinafter as "powders according to the invention" or "compositions according to the invention".
[0018] We have advantageously found that the composition of the present invention can provide the sustained release of nicotine (or its salt) when being maintained in the mouth. The composition also provides a convenient way to store nicotine, which can produce a product that is easier and / or safer to handle than nicotine, nicotine salts and other commercially available forms. The high load of nicotine (or its salt) can be achieved in the holes of the chemically bonded ceramic system, while still allowing the composition to release nicotine, so that it can be transported to a single entrance through the oral mucosa at a satisfactory rate, namely reaching a satisfactory degree. Therefore, the composition of the present invention is intended for use in the mouth, and can be provided to end users in any final product form as described herein, particularly when combined with a pH adjusting agent when the ceramic carrier cannot serve as a source of alkalinity.
[0019] By using the term "chemically bonded ceramic system" (or similar terms), we mean materials that can be formed at room temperature or slightly elevated temperatures (e.g., below about 200° C.) These systems act as carriers in the formulations of the present invention because they contain pores in which nicotine (or its salts) can be located.
[0020] The term "chemically bonded ceramic" generally refers to a system formed from a self-solidifying precursor material. Chemically bonded ceramic systems include non-hydrated ceramics, partially hydrated ceramics or fully hydrated ceramics. Therefore, in an embodiment of the present invention, the porous solid is based on a ceramic material formed from a self-solidifying precursor ceramic. Non-limiting examples of chemically bonded ceramic systems include those formed from calcium phosphate, calcium sulfate, calcium silicate, calcium aluminate and combinations thereof. Preferred compositions include those based on chemically bonded ceramic systems that consume a controlled amount of water to form a network after hydration of one or more suitable precursor substances. Precursor substances that may be mentioned in this regard include CaOAl2O3, (CaO) 12 (Al2O3)7, (CaO)3(Al2O3), (CaO)(Al2O3)2, (CaO)3(SiO2), (CaO)2(SiO2), and in particular calcium sulfate (e.g., calcium sulfate hemihydrate), alpha-tricalcium phosphate, and tetracalcium phosphate (Ca4(PO4)2O). All of these materials are capable of reacting with water at room temperature to form a chemically bonded ceramic system. The water can be provided in liquid form, or the precursor material can be exposed to a humid atmosphere for a sufficient period of time to allow the material to solidify and harden.
[0021] Other specific systems that can be used are those based on aluminates and silicates, both of which consume large amounts of water. Crystalline or amorphous phases such as CA2, CA, C3A and C12A7 as well as C2S and C3S (according to common cement terminology, C=CaO, A=Al2O3, SiO2=S) can be used, which are easily available. Calcium aluminate and / or calcium silicate phases can be used as separate phases or as a mixture of phases. All of the above phases are in non-hydrated form and act as a binder phase (cement) in the carrier when hydrated. The weight ratio of liquid (water) to cement is generally in the range of 0.2 to 0.5, preferably in the range of 0.3 to 0.4.
[0022] During manufacturing, particularly for chemically bonded ceramic systems formed from calcium aluminates and calcium silicates, the water to cement ratio is important for pore size and pore volume. For example, for a pure phase 1:1 CA precursor, the theoretical water to cement ("W / C") ratio to achieve complete hydration and full utilization of all water is about 0.4. If the W / C ratio is increased, any excess water present will result in an increase in pore volume and, to some extent, in pore size. For calcium aluminates and calcium silicates, the permissible range for water content is quite wide, i.e., the W / C ratio can be increased to well above the theoretical value required for complete hydration and still have a hardened body that has adequate structural integrity.
[0023] Specific ceramic materials that can be employed include those based on sulfates (such as calcium sulfate) or phosphates (such as calcium phosphate). Specific examples of such materials include α or β phase calcium sulfate hemihydrate (final product calcium sulfate dihydrate), basic or neutral calcium phosphate (apatite), and acidic calcium phosphate (brushite). In one embodiment, the chemically bonded ceramic system is formed from calcium sulfate (e.g., calcium sulfate hemihydrate).
[0024] The use of chemically bonded ceramic systems containing calcium may be particularly beneficial to the oral health of the user. Chemically bonded ceramic systems that can release calcium (e.g., in the form of dissolved calcium ions) into saliva can remineralize, and thus can, for example, contribute to the growth of minerals on the surface of the teeth. Materials that allow excess ions (e.g., calcium ions, hydroxide ions, and possibly phosphate ions) to diffuse into the surrounding saliva under physiological conditions (e.g., at the pH and temperature normally present in the oral cavity) may be particularly suitable for this, and such materials include chemically bonded ceramic systems formed by α-tricalcium phosphate and tetracalcium phosphate. Chemically bonded ceramic systems formed by materials other than calcium phosphate but still capable of releasing calcium into saliva are also useful in this case, because saliva can serve as a source of phosphate ions, thereby contributing to the growth of minerals such as apatite on the teeth. Such materials include chemically bonded ceramic systems formed by calcium silicate, calcium aluminate, and particularly calcium sulfate.
[0025] The composition of the present invention may contain any amount of carrier sufficient to maintain and deliver the desired amount of nicotine in use. In one embodiment of the present invention, the chemically bonded ceramic system is present in about 40% by weight to about 98% by weight of the powder composition. As described elsewhere herein, the final product (e.g., nicotine pouch and sublingual and buccal tablets) provided to the user generally has a mass of no more than 2 grams. In one embodiment of the present invention, the chemically bonded ceramic system is present in about 40% by weight to about 98% by weight of the final product (e.g., nicotine pouch).
[0026] The chemically bonded ceramic system used in the composition of the present invention can be loaded with nicotine or its salt by immersing the chemically bonded ceramic system in a liquid containing nicotine or its salt, or by any other method that helps to absorb the substance into the pores of the system via capillary forces, including spraying, brushing, roller coating, dipping, powder coating, atomization or vacuum enhanced loading.
[0027] In the example where the powder of the present invention also contains a pH adjusting agent, the pH adjusting agent may not be present during the process of loading the chemically bonded ceramic system with nicotine (or its salt). Instead, the pH adjusting agent may be added to the powder after the powder of the present invention is formed. Alternatively, the pH adjusting agent may be added to the chemically bonded ceramic system before or simultaneously with nicotine.
[0028] Intraoral formulations containing the compositions of the present invention, particularly nicotine pouches, may also be suitable for storage at ambient temperature without significant degradation of the components contained therein. Avoiding the need for refrigerated storage has obvious benefits for manufacturers, retailers and users of these products.
[0029] However, preferably, nicotine (or a salt thereof) is present when the chemically bonded ceramic system is formed. This allows for better control over the extent to which the pores in the chemically bonded ceramic system are filled with nicotine, and therefore allows for better control over the release characteristics of the final composition. In particular, this loading method enables more reliable control over the total amount of nicotine stored in and released from the chemically bonded ceramic system.
[0030] As described above, the chemically bonded ceramic system is formed by a suitable precursor material, such as calcium sulfate or calcium phosphate, which is generally provided in a powdered form for hydration. The average particle size of any precursor powder particles can be less than about 500 μm, for example less than about 100 μm, preferably between about 1 μm and about 30 μm. This is to enhance hydration. Such precursor materials can be converted into nano-sized microstructures during hydration (for example, when in contact with liquid water or a humid atmosphere). The reaction involves the dissolution of the precursor material and the subsequent repeated precipitation of nano-sized hydrates in water (solution) and on the remaining unhydrated precursor material. The reaction advantageously continues until the precursor material has been converted and / or until the preselected porosity determined by partial hydration using time and temperature and H2O and / or humidity in the liquid is measured.
[0031] In the process of manufacturing the network structure of the carrier material, the pore size in the chemically bonded ceramic system can be controlled by various techniques. A specific method suitable for use with the chemically bonded ceramic system used in the present invention is a porogen leaching method, which involves the use of a sacrificial phase during the formation of the chemically bonded ceramic system. During the formation of the chemically bonded ceramic system, a porogen can be included as part of the reaction mixture to help form pores in the final carrier material network. Porosity materials include, for example, oils, liquids (such as water), sugars, mannitol, etc. The porogen can then be removed from the carrier, for example, by heating it during the curing process, or by using a suitable solvent to dissolve it. Dissolution is usually achieved with water to avoid leaving a residual amount of material that may have a harmful effect on the formulation or have an adverse effect on the user. In this case, nicotine or its salt can then be loaded into the pores in the chemically bonded ceramic system by any method disclosed elsewhere herein. Porosity materials with secondary functions can also be used. For example, porogens can be used as a source of flavoring agents, such as sweeteners. In this case, it is not necessary to remove the porogen from the carrier before use. Instead, some or all of the porogen may be retained in the carrier along with the nicotine (or its salt) so that both substances can be released in the user's mouth. Porosity-forming materials that dissolve rapidly in water are particularly suitable for use in this manner. Furthermore, porogens that dissolve slowly in water can be used to control the release of alkaline active agents, for example when sustained release is desired. Porosity-forming materials that can be used as sweeteners include sweeteners known in the art, particularly monosaccharides, oligosaccharides and polysaccharides; sugar alcohols such as mannitol, sorbitol, maltitol and xylitol; natural and synthetic sweeteners such as sucrose, glucose, dextrose, maltose, fructose, saccharin, aspartame, acesulfame potassium, sucralose, saccharin and sodium cyclamate; and mixtures thereof.
[0032] Foaming methods can also be used to increase the pore size in chemically bonded ceramic systems. Such methods are known to those skilled in the art and are particularly useful for forming supports with larger pore sizes. An example of such a method includes preparing the support using carbonated water or water containing bubbles. This can also be achieved without the use of a foaming agent (e.g., Tween 80).
[0033] The total porosity of the chemically bonded ceramic system can be from about 10% to about 70%, such as from about 20% to about 40%. The porosity and average pore size can be measured by methods known to those skilled in the art, such as mercury intrusion, BET (Brunauer, Emmet and Teller) method and N2-adsorption technique.
[0034] In a preferred embodiment of the invention, nicotine (or its salt) is co-formedly dispersed in the pores within the network of the carrier material. This means that, whatever method is used to form the carrier, it must also form pores in which the nicotine is dispersed. When the method of forming the carrier involves the use of a porogen, the nicotine will also be dispersed in the pores directly generated by the use of the porogen. Chemically bonded ceramic systems are particularly suitable for use in such embodiments because the process of forming the carrier and its pore network does not require very high temperatures compared to sintered ceramics.
[0035] Nicotine (or its salt) can be mixed with the precursor of chemically bonded ceramic system using a variety of techniques (such as dry powder mixing). Alternatively, nicotine (or its salt) and precursor can be mixed by sol-gel method in the presence of suitable liquid (such as aqueous or organic solvent), as solution, or as slurry, paste or putty of particles, granules or pellets of the precursor, such as the precursor. This mixing step is followed by a certain type of "curing" process to form a chemically bonded ceramic system, which contains holes in which nicotine resides. The chemically bonded ceramic system formed in this way can be said to be pre-loaded with nicotine.
[0036] Such pores themselves are a three-dimensional network of channels or voids within the solid network, containing nicotine or a salt thereof (eg, particles thereof).
[0037] Such pores may thus be essentially "secondary pores" formed by chemical interactions (e.g. "bonding") between surfaces of primary particles of the support (which may themselves be porous (i.e. contain "primary" pores). For example, such porosity may result from exposure of such material to one or more chemical agents which cause a physical and / or chemical transformation (such as partial dissolution) at these surfaces and subsequently cause these surfaces to physically and / or chemically bond together (which may itself be the result of some other physicochemical process such as drying, curing, etc.), thereby generating the pores / voids.
[0038] In this case, the chemical agent may be mixed with the nicotine before or during the preparation of the chemically bonded ceramic system. However, such secondary pores are not necessarily formed in this way, and the bonding of the primary particles of the chemically bonded ceramic material together may also be physical and / or mechanical, or may be formed in the presence of nicotine during the production of the three-dimensional chemically bonded ceramic network as described above.
[0039] Preferably, the precursor of the chemically bonded ceramic system is mixed with nicotine (or its salt) before the hardening process is performed. Nicotine is then present at the moment of pore formation, and as a result, nicotine becomes located in the pores of the chemically bonded ceramic system. Good control of the total amount of nicotine loaded into the preparation can be achieved by processing in this way. Therefore, in one embodiment, at least a portion of nicotine (or its salt) is located in the pores of the (hardened) chemically bonded ceramic system. Thus, we refer to at least 20% by weight (e.g., at least 30% by weight, at least 40% by weight, at least 50% by weight, at least 60% by weight, at least 70% by weight, or at least 80% by weight) of nicotine (or its salt) being located in the pores of the chemically bonded ceramic system. In one embodiment, at least 80% by weight of nicotine (or its salt) is located in the pores of the chemically bonded ceramic system. In another embodiment, substantially all of nicotine (or its salt) is located in the pores of the chemically bonded ceramic system. By this we mean that at least 90 wt. % (eg at least 95 wt. %, preferably at least 98 wt. %) of the nicotine (or its salt) is located within the pores of the chemically bonded ceramic system.
[0040] The amount of nicotine (or its salt) present in the composition of the present invention can vary significantly depending on its intended use, the intended form of the oral formulation and the intended release profile. For example, the composition may contain nicotine or its salt in an amount of 0.1% to 50% by weight of the composition (i.e., powder).
[0041] Composition of the present invention is intended to be used for the oral delivery of nicotine, for both treatment and entertainment purposes. Powdered composition can be used for making oral preparations, and it provides a substitute for tobacco products (such as cigarettes and tobacco-containing snuff), and therefore can be used to reduce the many potential toxic components found in tobacco products that users are exposed to. Nicotine is obtained from tobacco products conventionally, such as tobacco oil and other extracts. For example, nicotine can be used as free alkali (for example, as a mixture of nicotine free alkali and porous particle carrier such as microcrystalline cellulose), nicotine salt (for example, as another organic acid salt of nicotine tartrate or nicotine bitartrate or nicotine), as the resin complex of nicotine (for example, nicotine ion exchange resin) or as solvate or other suitable forms provide.
[0042] Preferably, some or all of the nicotine is present in the composition of the present invention in the form of nicotine in a water-soluble form. In this article, the term "water-soluble form" is understood to refer to a nicotine form having a solubility of at least 10 g per 100 mL of water in water under ambient conditions (including a temperature of 25 ° C, atmospheric pressure, and a pH of 7). It is believed that the nicotine present in the composition of the present invention exists as (at least mostly) amorphous material. The method for forming the chemically bonded ceramic system used in the present invention includes hydrating a suitable precursor material in the presence of nicotine (or its salt), followed by a hardening step. At the beginning of the manufacturing process, nicotine or its salt is preferably provided in the form of a crystalline solid because a high-purity crystalline solid can be easily obtained. In this process, nicotine (or salt) is dissolved and / or diluted in a hydrating liquid, and a subsequent drying step causes an amorphous nicotine product to precipitate in the pores of the chemically bonded ceramic system. The amorphous nicotine product can be a salt of nicotine. Powder X-ray crystallography can be used to detect the presence of crystalline components (such as nicotine salts), and other methods for detecting and quantifying crystallinity and / or amorphism are known in the art.
[0043] In one embodiment, the composition of the present invention uses a salt of nicotine, such as nicotine tartrate (e.g., nicotine bitartrate dihydrate) to prepare. Other salt forms that may be mentioned include nicotine ascorbate, nicotine aspartate, nicotine benzoate, nicotine monotartrate, nicotine chloride (e.g., nicotine hydrochloride and nicotine dihydrochloride), nicotine citrate, nicotine fumarate, nicotine gentisate, nicotine lactate, nicotine mucate, nicotine laurate, nicotine levulinate, nicotine malate, nicotine perchlorate, nicotine pyruvate, nicotine salicylate, nicotine sorbate, nicotine succinate, nicotine zinc chloride, nicotine sulfate, nicotine tosylate and hydrates thereof (e.g., nicotine zinc chloride monohydrate). For the avoidance of doubt, in the case of using a salt of nicotine to prepare the composition of the present invention, nicotine may be present in the final composition as nicotine free base, a salt of nicotine (e.g. nicotine bitartrate) or a mixture thereof. In addition, the nicotine in the composition may be mostly (e.g. at least 70%) amorphous.
[0044] As described elsewhere herein, the composition of the present invention can be incorporated into a pouch similar to snuff. Snuff typically contains ground tobacco. However, in a particular embodiment, the composition of the present invention does not contain ground tobacco. It is believed that the nicotine (or its salt) in the powder composition of the present invention has enhanced stability characteristics compared to commercially available products, i.e., compared to compositions in which nicotine is not stored in the pores of a chemically bonded ceramic carrier of the type disclosed herein. Without wishing to be bound by theory, it is believed that the composition of the present invention prevents or slows the oxidation of nicotine, thereby extending the shelf life of the product. The composition is able to maintain its sustained release properties even after long-term storage.
[0045] In addition, the powder composition of the present invention is advantageous because they provide safe storage means for nicotine (or its salt).Pure nicotine is classified as having acute toxicity and is irritating to skin and eyes.Therefore, the manufacture and processing of pure nicotine are challenging, and the end-user product that has the risk of exposing the user to liquid during use (such as during refilling) is very undesirable.The powder composition of the present invention overcomes these risks by providing nicotine in a solid form of dilution.In this form, nicotine can be easily processed, and the risk of user exposure to nicotine is greatly reduced.The powder composition of the present invention also has the improved safety of nicotine (such as microcrystalline cellulose loaded with nicotine) that is superior to other solid forms, because the latter is easy to release nicotine (usually in salt form) in dust form.By contrast, the powder composition of the present invention is more effective in combining nicotine in a carrier to avoid releasing before the predetermined time.
[0046] The rate at which nicotine is absorbed into the body via the oral mucosa varies depending on the pH of the saliva. Tomar SL et al. (Tobacco Control 1997; 6: 219-225) reported that increasing alkalinity promotes the absorption of nicotine and enhances its physiological effects. Therefore, a pH regulator may be present in the composition of the present invention to enhance the rate and extent of transmucosal uptake of nicotine.
[0047] The preparation of oral formulations containing sufficient amounts of nicotine (or its salt) and pH modifiers is difficult. We have found that during the process of forming a hardened porous chemically bonded ceramic system, a significant proportion of the nicotine may be lost. Without wishing to be bound by theory, it is believed that the main mechanism of loss is evaporation.
[0048] We have surprisingly found that by hardening and solidifying the chemically bonded ceramic system in the absence of any pH adjusting agent, this evaporation loss can be greatly reduced or essentially completely eliminated. Therefore, in a second aspect of the present invention, a method for forming a powder composition of the present invention is provided, wherein the method includes forming a chemically bonded ceramic system in the absence of a pH adjusting agent. All embodiments and preferences disclosed herein related to the composition of the present invention are also disclosed in connection with the method. The present invention also relates to a powder composition obtainable (or obtained) by the method.
[0049] Nicotine (or its salt) may still be present during the hardening stage, i.e. nicotine may be mixed with the precursor material of the chemically bonded ceramic system, with the result that good control of the nicotine load may be achieved. Therefore, in one embodiment of the composition of the present invention, the chemically bonded ceramic system is formed in the presence of nicotine or its salt. The pH regulator may then be introduced after the chemically bonded ceramic system has hardened without evaporation losses of nicotine occurring.
[0050] References herein to methods and compositions in which a chemically bonded ceramic system is formed in the presence of nicotine or a salt thereof include methods and compositions in which a chemically bonded ceramic system is formed with only a portion (but not all) of the nicotine present in the final product. In this manner, the pores of the hardened chemically bonded ceramic system contain up to 99% by weight (such as up to 95% by weight, up to 90% by weight, up to 80% by weight, or up to 70% by weight) of the total amount of nicotine or a salt thereof in the final product.
[0051] Typically, once a hardened mass of chemically bonded ceramic (e.g., a hardened mass of a chemically bonded ceramic system loaded with nicotine or its salt) is formed, it is ground to form a powder. If desired, the powder can then be mixed with a pH adjusting agent. The grinding process can also be carried out in the presence of a pH adjusting agent to ensure effective mixing.
[0052] If the pH adjuster is not present during the formation of the chemically bonded ceramic system, the pH adjuster will not be incorporated into the pores of the chemically bonded ceramic system. When the two components are combined together or during subsequent processing, a small amount of pH adjuster may enter the pores of the chemically bonded ceramic system, but only a very small amount of entry will occur in this way. Therefore, in one embodiment, the pH adjuster is mainly located outside the pores of the chemically bonded ceramic system. By this, we mean that at least 90% by weight (e.g., at least 95% by weight, preferably at least 98% by weight) of the pH adjuster is located outside the pores of the chemically bonded ceramic system.
[0053] The term "pH adjusting agent" refers to any substance that can change the pH of normal saliva. The pH of normal saliva is around 6.8. The pKa of nicotine is about 8.02 (Tomar SL et al., Tobacco Control 1997; 6: 219-225). The absorption of nicotine from the oral cavity to the systemic circulation (i.e., transmucosal uptake) depends on the local pH of the saliva inside and near the product in use. Nicotine is mainly absorbed through the mucosa in a non-protonated form. Therefore, it is preferred to provide a local pH that causes a high proportion of nicotine to be non-protonated. For this reason, alkaline conditions enhance the transport of nicotine through the oral mucosa and into the bloodstream, and therefore it is preferred that the pH adjusting agent is an alkaline agent, i.e., a substance that can increase the pH of saliva to above normal. Alkaline buffers are also considered herein. The term "alkaline buffer" can be used interchangeably with "alkaline buffer" and refers to a reagent for obtaining a buffer solution with an alkaline pH. Preferred alkaline agents are buffers selected from the group consisting of carbonate (including bicarbonate), silicate, aluminate, acetate, glycinate, phosphate, glycerophosphate, citrate such as alkali metal citrate and borate, hydroxide or its mixture. In one embodiment, a strong base such as sodium hydroxide, potassium hydroxide or its mixture is used. In a particular embodiment, carbonate (including bicarbonate) or phosphate (including triphosphate) compounds can be used as pH adjusting agents. Such compounds can form salts with any suitable cation such as sodium, potassium, calcium or magnesium. Specific pH adjusting agents that can be mentioned include sodium carbonate, sodium bicarbonate, trisodium phosphate and combinations thereof.
[0054] Other examples of pH adjusting agents that can be used include calcium aluminate, calcium silicate, calcium phosphate and calcium carbonate, as well as chemically bonded ceramic systems made of any of these calcium salts (as described elsewhere herein), and mixtures thereof. For the avoidance of doubt, any pores in the chemically bonded ceramic system do not necessarily contain nicotine or its salt. When a chemically bonded ceramic system made of any calcium salt mentioned herein is used as a pH adjusting agent, the system is formed before it is added to the other components of the composition of the present invention (e.g., by hardening the hydrated substance of the calcium salt). The pH adjusting agent in such an example may be referred to as a "second" chemically bonded ceramic system. The composition of the present invention already contains a chemically bonded ceramic system (formed in the absence of a pH adjusting agent), so it may be referred to as a "first" chemically bonded ceramic system.
[0055] In a specific example of such a composition of the present invention, the second chemically bonded ceramic system (i.e., pH adjuster) may be formed of calcium aluminate, and the first chemically bonded ceramic system may be formed of calcium sulfate (preferably in the absence of the second chemically bonded ceramic system). Once the first chemically bonded ceramic system is formed, it may be loaded with nicotine or a salt thereof by a method such as soaking the first chemically bonded ceramic system. However, the first chemically bonded ceramic system is preferably formed in the presence of nicotine of its salt (and preferably in the absence of the second chemically bonded ceramic system).
[0056] The amount of the pH adjusting agent present in the composition is generally selected to be sufficient to raise the pH at the application site to at least 8. Alternatively, a chemically bonded ceramic system acting as a source of alkalinity can be used as a carrier of nicotine. Preferably, the pH is not increased too much to avoid damage to the tissue in the oral cavity. Therefore, in another embodiment, the composition of the present invention can provide a pH of up to 9.5 (e.g., up to 9, up to 8.8, or up to 8.5) when in contact with saliva. In an embodiment of the present invention, the composition comprises the pH adjusting agent in an amount of at least 0.1% by weight of the composition, particularly at least 0.5% by weight. For example, the composition may comprise the pH adjusting agent in an amount of 0.1% to 50% by weight of the composition, such as about 1% to about 10% by weight of the composition. Such weight is particularly suitable for compositions in which the pH adjusting agent is sodium carbonate, i.e., when the pH adjusting agent is sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), or a mixture thereof.
[0057] In some embodiments, the pH adjuster is a buffer comprising sodium carbonate and sodium bicarbonate, for example in a weight ratio between 5: 1 and 2.5: 1, preferably in a weight ratio between 4.1: 1 and 3.5: 1. A specific buffer that may be mentioned is the sodium carbonate-sodium bicarbonate buffer system.
[0058] The present invention relates to powder. Unless otherwise stated, when used in this article, the term "powder" refers to any solid material in the form of particles. This includes particles and granules, usually with an average particle size of not more than 1mm. The powder is preferably flowable, so as to facilitate transportation, storage and subsequent processing into the final product, such as described elsewhere herein (such as snuff products). When stored, the powder can also be in a state of non-flowability or poor fluidity, but when subjected to suitable conditions such as ventilation or shear force, it is easy to increase fluidity. The powder can be stored in any suitable container, preferably in an airtight container, for storage and transportation. The powder can also be manufactured, stored, transported and / or further processed on a small scale and on a large scale (such as about 1 gram to about 1 ton). In an embodiment of the present invention, a container (such as a sealed or airtight container) is provided, which contains at least 1g (such as at least 10g, at least 100g, at least 1kg, at least 10kg, at least 100kg or at least 1000kg) of the powder of the present invention.
[0059] Extended flavor release
[0060] It is also found that the solid porous chemically bonded ceramic system disclosed herein about the first aspect of the present invention is surprisingly effective in providing extended release of flavoring agents in the mouth. As shown in the examples, dry powders containing such ceramic systems (wherein one or more flavoring agents are loaded into the pores of the ceramic) are surprisingly able to release flavoring agents at a sufficient rate and sufficient time, thereby providing users with a meaningful sensory experience, which is much longer than the time achieved by commercial preparations. In some cases, the flavoring duration using the composition of the present invention is almost twenty times that of commercial products.
[0061] Thus, according to a third aspect of the invention, there is provided a combination of a solid porous chemically bonded ceramic system as disclosed herein and a flavoring agent, for example in powder form. The flavoring agent is incorporated into the pores in the chemically bonded ceramic system using any of the methods described above for nicotine. Thus, the preferences and embodiments described elsewhere herein for nicotine products are equally applicable to embodiments involving a combination of a solid porous chemically bonded ceramic system and a flavoring agent.
[0062] In one embodiment, the chemically bonded ceramic system used in the formulation of the present invention is loaded with flavoring (or flavorings) by immersing the chemically bonded ceramic system in a liquid containing a flavoring, or by any other method that helps to absorb the flavoring into the pores of the system via capillary forces (including spraying, brushing, roller coating, dipping, powder coating, spraying or vacuum enhanced loading). For example, some flavorings can be provided as liquid products, such as solutions, suspensions or emulsions. Such liquid products can be contacted with the chemically bonded ceramic system by simply mixing two components so that the flavoring is incorporated into the pores in the ceramic. As shown in the examples, the ceramic pores can also contain nicotine before the flavoring is introduced, and the product can still provide extended release of both nicotine and flavorings.
[0063] In another embodiment, the flavoring agent is co-formatively dispersed within the pores of the chemically bonded ceramic system. For example, a precursor to the chemically bonded ceramic system can be mixed with the flavoring agent (or flavoring agents) before the hardening process is performed. The flavoring agent (optionally with nicotine or a salt thereof) is then present at the moment of pore formation, with the result that the flavoring agent becomes located within the pores of the chemically bonded ceramic system.
[0064] Examples of flavoring agents include the sweeteners and flavoring agents (or "flavorings") described elsewhere herein. For the avoidance of doubt, this includes sugars such as sucrose, glucose, dextrose, maltose and / or fructose, sugar alcohols such as mannitol, xylitol, sorbitol, maltitol and / or isomalt, or artificial sweeteners such as sucralose, sodium cyclamate, aspartame, acesulfame potassium and / or saccharin.
[0065] Other flavorings that can be used, particularly in nicotine pouches, include menthol, peppermint, wintergreen, sweet mint, spearmint, vanillin, chocolate, black cherry, coffee, cinnamon, cloves, tobacco, citrus, fruit flavorings, and mixtures thereof. In one embodiment, the flavoring is not tobacco or nicotine. Such flavorings can be present in the combination in an amount of at least 0.1% by weight of the combination of the solid porous chemically bonded ceramic system and the flavoring (or flavorings), and preferably no more than 50% by weight.
[0066] The flavoring agent may be used in combination with any chemically bonded ceramic system described elsewhere herein. For the avoidance of doubt, this includes any chemically bonded ceramic system formed from calcium phosphate, calcium sulfate, calcium silicate, calcium aluminate, magnesium carbonate, or a combination thereof. Preferred chemical compositions include those based on chemically bonded ceramic systems that consume a controlled amount of water to form a network after hydration of one or more suitable precursor materials. Precursor materials that may be mentioned in conjunction with the third aspect of the invention include CaOAl2O3, (CaO) 12(Al2O3)7, (CaO)3(Al2O3), (CaO)(Al2O3)2, (CaO)3(SiO2), (CaO)2(SiO2), and in particular α-tricalcium phosphate, tetracalcium phosphate (Ca4(PO4)2O) and calcium sulfate (e.g. calcium sulfate hemihydrate).
[0067] The combination according to the third aspect of the present invention can be used to manufacture oral products, such as oral products of the type described herein, and food products (such as chewing gum, candy, mints, etc.) and health products intended to be kept in the mouth for a long time (such as more than 5 minutes). In one embodiment, they can be used to manufacture nicotine pouches, such as by adding the combination to nicotine (or its salt) before being loaded into the pouch according to any method disclosed herein. The combination according to the third aspect of the present invention can advantageously be provided as a powder for this purpose or any other purpose, because the combination can be supplied as an easily handled powder. Such combinations can be stored in any suitable container, such as an airtight container. For manufacturing purposes, they can also be supplied in any quantity, such as 1g to 100kg.
[0068] In a further embodiment, there is provided a pouch (eg a non-woven pouch) containing the combination according to the third aspect of the invention.
[0069] Oral preparations
[0070] The powder composition of the present invention can release nicotine (or its salt) when exposed to the moisture in the mouth. Therefore, the composition can be used to manufacture final products, such as nicotine pouches (similar to snuff) and sublingual and buccal tablets, which are designed for oral use, and for example, the composition can be suitable for use in pouches, for releasing nicotine or its salt when the pouch is placed in the mouth. "Final product" and "oral preparation" mentioned herein include products mentioned containing the powder composition of the present invention. The powder of the present invention can also be used to manufacture other products, such as pharmaceutical preparations containing nicotine (or its salt). Because the powder of the present invention provides a nicotine form that can be safely stored for a long time and is easy to handle during the manufacture of the final product (such as nicotine pouches or pharmaceutical preparations), it is therefore advantageously possible to prepare in batches, store and transport powder.
[0071] The composition of the present invention is particularly suitable for transmucosal administration, whereby an intraoral formulation containing the composition (e.g. in the form of a sachet) is placed in contact with the lips, gums or cheeks for an extended period of time (several minutes) as the nicotine is released. Since the increased alkalinity in saliva enhances the rate and extent of transmucosal uptake of nicotine, the powder of the present invention is preferably capable of providing a pH of at least 8 when in contact with saliva.
[0072] As used herein, the terms "pouch" and "nicotine pouch" refer to a pouch or bag that is fully or partially loaded with the composition of the present invention. Nicotine pouches containing the composition of the present invention can be described as a tobacco-free version of snus. In such systems, the pouch or bag contains a specific amount of the composition, and thus a specific amount of nicotine, but generally does not include any tobacco dust, leaves or stems.
[0073] Embodiments of the present invention relate to a nicotine pouch comprising a permeable sealed bag containing a composition of the present invention. The bag is generally made of a permeable material that closes a cavity. The powder composition remains in the cavity, but when the bag is exposed to water (e.g., saliva), the soluble components of the composition can pass through the bag material. Suitable materials for nicotine pouches are known to those skilled in the art, and include paper, filter paper, etc. of the type used in tea bags. Other materials include heat-sealable nonwoven cellulose, such as long fiber paper, cotton, and silk.
[0074] Although in some embodiments, the powder in the nicotine pouch contains a pH adjusting agent, alternatively or additionally, a certain amount of pH adjusting agent may be present and combined with the bag material itself. For example, particles of a pH adjusting agent (e.g., sodium carbonate and / or sodium bicarbonate) may be embedded in the permeable material of the bag so that the pH adjusting agent can be easily dissolved when in contact with saliva. The pH adjusting agent combined with the bag material may be the same or different from any pH adjusting agent in the powder. Therefore, in one embodiment, the bag includes a cavity surrounded by a permeable material, and at least a portion of the pH adjusting agent in the product is combined with the permeable material. Suitable methods for incorporating pH adjusting agents or nicotine into the bag material are known to the technician.
[0075] For the avoidance of doubt, it is not necessary that all nicotine in the final product is located in the hole of the chemically bonded ceramic system. Some nicotine may be located outside the hole. For example, in the case where the final product is a pouch containing a powdered composition, a portion of nicotine (preferably a powdered salt of nicotine) can be mixed with a powdered chemically bonded ceramic system (which itself can include a hole containing a certain amount of nicotine or its salt) before being placed in the pouch. The mixing can be achieved by spraying a nicotine solution onto the particles of the chemically bonded ceramic system of the load nicotine, and then drying the mixture before being placed in the pouch. In such embodiments, the amount of nicotine (or its salt) added to the hardened powdered chemically bonded ceramic system is 1 to 50 weight %, 5 to 40 weight % or 10 to 30 weight % of the total amount of nicotine (or its salt) in the final product.
[0076] In a further example, where the final product is provided in the form of a pouch containing a powdered composition, a portion of the nicotine in the product may be combined with the material forming the pouch, i.e., a portion of the nicotine is not located in the cavity of the pouch (as described elsewhere herein), but is incorporated into or incorporated into the wall of the pouch itself. This can be achieved, for example, by soaking the pouch material in a solution containing nicotine (as a base or dissolved nicotine salt), and then allowing the solvent (e.g., water or another suitable solvent) to evaporate, so that nicotine or its salt is incorporated into the pouch material. In embodiments where the final product is provided in the form of a pouch containing a powdered composition and a portion of the nicotine in the final product is combined with the material forming the pouch, the amount of nicotine (or its salt) combined with the material can be 0.1 to 30% by weight, 0.5 to 20% by weight, or 1 to 10% by weight of the total amount of nicotine (or its salt) in the final product.
[0077] In an embodiment of the present invention, the powder is contained in a pouch, and the gross weight of the pouch of the load is 0.2 to 3g, such as 0.4 to 2g. In another embodiment, the nicotine pouch has a weight and / or volume similar to commercially available portioned snus products and nicotine pouches. In a further embodiment of the present invention, the powder is contained in a pouch having a gross weight of 0.1 to 0.5g, such as 0.1 to 0.4g. Pouches are discussed elsewhere herein, and due to the fact that the chemically bonded ceramic system mentioned herein can provide very compact and stable storage of nicotine, while maintaining a suitable release curve, the utility of this low weight product is possible.
[0078] The nicotine pouches may be prepared using methods known to those skilled in the art, particularly those used to make snus and commercially available nicotine pouches such as ) are manufactured by those methods described herein or known in the art. For example, the powdered contents for the pouch can be prepared using the methods described herein or using conventional methods known in the art, and then the powder can be loaded into a sealable bag, such as a heat-sealable bag. Such bags should be water-insoluble and permeable to saliva. Suitable materials for nicotine pouches have been described above, and are also known to the technician, such as known from the example of U.S. Patent No. 9,161,908. Heat-sealable non-woven cellulose, such as long fiber paper, provides a material particularly suitable for nicotine pouches. Once a prescribed amount of powder is filled into the pouch, it is kept in the pouch by sealing. Nicotine can be promoted to be taken in the mouth by incorporating a bioadhesion and / or mucoadhesion promoter into the nicotine pouch. The bioadhesion and / or mucoadhesion promoter can be provided in the cavity of the bag. Alternatively or additionally, the agent can be incorporated into the bag material or combined with the bag material.
[0079] Intraoral products based on tablets that can be mentioned include sublingual tablets, buccal tablets, thin slices and lozenges. In this form, the intraoral product containing the powder composition of the present invention is intended to be placed under the tongue, under the lips, against the gums or against the cheek, and nicotine (or its salt) is absorbed by the surrounding mucosa. Such preparations are particularly useful for providing low doses of nicotine to users to meet the urgent need or desire for nicotine. Unless otherwise stated, reference to "sublingual tablets" elsewhere herein includes reference to buccal tablets. Adhesion to the inner surface of the oral cavity can be promoted by incorporating bioadhesion and / or mucoadhesion promoters into tablets, thin slices or lozenges.
[0080] Bioadhesion and / or mucoadhesion promoters effectively make pouches or sublingual tablets adhere to oral mucosa. The expression "mucoadhesion" is intended to indicate adhesion to mucosa covered by mucus (such as mucosa in the oral cavity), while the expression "bioadhesion" is intended to indicate adhesion to biological surfaces (including mucosa not covered by mucus) more generally. These expressions are usually overlapping as definitions, and can usually be used interchangeably, although the expression "bioadhesion" has a slightly wider range. In this specification and claims, these two expressions have the same purpose for the purpose of the present invention, and this has been expressed by using the general term "biological / mucoadhesion". Suitably, the oral preparation contains 0.1 to 25 weight % of the biological / mucoadhesion promoting compound based on the gross weight of the preparation.
[0081] Preferably, the bio / mucoadhesion promoter is a polymeric substance, preferably a substance having an average molecular weight greater than 5,000 Daltons (weight average). A variety of polymers known in the art can be used as bio / mucoadhesion promoters. Examples of such bio / mucoadhesion promoters include cellulose derivatives such as hydroxypropyl methylcellulose (HPMC), hydroxyethylcellulose (HEC), hydroxypropyl cellulose (HPC), methylcellulose, ethyl hydroxyethylcellulose, carboxymethylcellulose, modified cellulose gum, and sodium carboxymethylcellulose (NaCMC); starch derivatives such as moderately cross-linked starch, modified starch, and sodium starch glycolate; acrylic acid polymers such as carbomer and its derivatives etc.); polyvinyl pyrrolidone; polyethylene oxide (PEO); chitosan (poly-(D-glucosamine)); natural polymers such as gelatin, sodium alginate and pectin; scleroglucan; xanthan gum; guar gum; poly-co-(methyl vinyl ether / maleic anhydride); microcrystalline cellulose and cross-linked carboxymethylcellulose (e.g., cross-linked sodium carboxymethylcellulose). Such polymers can be cross-linked. Combinations of two or more bio / mucoadhesive polymers can also be used.
[0082] Nicotine pouches and sublingual tablets may also contain one or more other ingredients selected from the group consisting of fillers (typically food grade fillers), water, salt and flavorings. It is not necessary to incorporate any of these other ingredients into the pores of the chemically bonded ceramic system, however, any such ingredients that are incorporated in this manner and are water soluble will be expected to have a release profile similar to that of the nicotine contained within those pores.
[0083] Fillers that increase saliva production can also be advantageously used in the products described herein. Such substances are sometimes referred to as salivating agents, are known in the art and include salt (NaCl), sweeteners (e.g., xylitol), and acidic substances (such as malic acid and ascorbic acid). The nicotine in the powder can be dissolved in saliva and then absorbed through the oral mucosa. The flavorings in the product are also transported to the taste buds in the oral cavity through saliva. By ensuring that the sensations caused by the nicotine and flavorings in the product can occur faster, the incorporation of substances that increase saliva production improves the user's experience.
[0084] Other fillers that can be used in nicotine pouches include gum arabic, microcrystalline cellulose, maltitol. Further fillers that may be mentioned include inert inorganic fillers such as alumina, zirconia and glass.
[0085] Fillers are typically present in the oral formulation in an amount of about 10% to about 90% by weight of the oral formulation.
[0086] A controlled release agent may also be incorporated into the formulation. Such agents slow down the rate at which nicotine is released from the product, thereby extending the duration of the sensory experience of the user. Preferably, the controlled release agent is a material that can provide sustained release, delayed release, or both.
[0087] In this respect, it is preferred that the controlled release agent is a polymer. Examples of polymers that can be used as controlled release agents include, but are not limited to, alkylcellulose polymers (e.g., ethylcellulose polymers) and acrylic polymers (e.g., acrylic acid and methacrylic acid copolymers, methacrylic acid copolymers, methyl methacrylate copolymers, ethoxyethyl methacrylate, cyanoethyl methacrylate, methyl methacrylate, copolymers, methacrylic acid copolymers, methyl methacrylate copolymers, methyl methacrylate copolymers, methacrylate copolymers, methacrylate copolymers, aminoalkyl methacrylate copolymers, methacrylic acid copolymers, methyl methacrylate copolymers, polyacrylic acid, polymethacrylic acid, methacrylic acid alkylamide copolymers, poly(methyl methacrylate), poly(methacrylic acid) (anhydride), methyl methacrylate, polymethacrylate, methyl methacrylate copolymers, poly(methyl methacrylate), poly(methyl methacrylate) copolymers, polyacrylamide, aminoalkyl methacrylate copolymers, poly(methacrylic anhydride) and glycidyl methacrylate copolymers). The polymer can also be a mixture of polymers. Typically, the polymer has a molecular weight (weight average and / or number average) of 1,000 to 10,000,000, 10,000 to 1,000,000, preferably 50,000 to 500,000 g / mol as measured by gel permeation chromatography.
[0088] Preferred polymers include the alkyl cellulose polymers and acrylic acid polymers described herein.
[0089] In order to improve the organoleptic properties of the preparation of the present invention, one or more sweeteners or texture modifiers may be added. These substances include sugars such as sucrose, glucose, dextrose, maltose and / or fructose, sugar alcohols such as mannitol, xylitol, sorbitol, maltitol and / or isomalt, or artificial sweeteners such as sucralose, sodium cyclamate, aspartame, acesulfame and / or saccharin. Sweeteners are particularly useful for masking the taste of nicotine in oral preparations.
[0090] Other flavorings that can be used, particularly in nicotine pouches, include menthol, peppermint, wintergreen, sweet mint, spearmint, vanillin, chocolate, black cherry, coffee, cinnamon, cloves, tobacco, citrus, fruit flavorings, and mixtures thereof. In one embodiment, the flavoring is not tobacco. The composition of the present invention can be used with any flavoring or combination of flavorings. Such flavorings can be present in an amount of at least 0.1% by weight of the nicotine pouch and preferably no more than 5% by weight.
[0091] Substances that provide a cooling mouthfeel, such as sugar alcohols (eg, erythritol), may be used in the oral formulations disclosed herein.
[0092] In one embodiment, the present invention relates to dry powders. The terms "dry powder" and "dry formulation" mean that the powder does not contain any component (except nicotine) that is liquid or low melting solid under ambient conditions. Nicotine is retained in the pores of the carrier, resulting in the powder having the characteristics of a dry solid.
[0093] It is also found that the dry formulation of the present invention provides a rapid release of water-soluble components. Studies involving human volunteers have found that the dry formulation of the present invention has a faster onset of sensation associated with the flavoring agent than the dry commercial formulation. The time required for the onset of nicotine sensation of the dry formulation of the present invention is equal to or less than the time required for the commercial dry formulation. Therefore, the formulation of the present invention can produce a rapid sensory experience for the user.
[0094] In another embodiment, the present invention relates to slightly wet powder. Slightly wet powder is a composition of the present invention, which additionally contains a component (except nicotine) that is liquid or low melting point solid under ambient conditions. Suitable components are known in the art and include glycerol, propylene glycol ("PG", E1520), polyethylene glycol (PEG) and sodium alginate (E401). Adding relatively small amounts of such components advantageously combines the smallest particles together to minimize the formation of fine dust. Fine dust can pass through the kind of non-woven fabric commonly used to make nicotine pouches, or block the holes therein. Typically, after the powder has been formed (for example, by crushing larger solid blocks), and optionally after the coarse particles of the chemically bonded ceramic system have been removed, a liquid or low melting point solid is added. The technician will be able to determine the amount of liquid or low melting point solid that needs to be added to the powder of the present invention. A suitable amount can be in the range of 0.1% by weight to 10% by weight (such as 2% by weight to 5% by weight) of the powder. Preferably, the amount is low enough to produce a powdered material that is easy to manufacture, handle, transport, divide and / or process.
[0095] The pouch containing slightly moist powder can be referred to as slightly moist pouch. Compared with dry pouch, slightly moist pouch usually feels more comfortable in the mouth, and usually provides faster initial release of nicotine. However, we find that slightly moist powder of the present invention also has surprising sustained release characteristics, similar to dry powder. That is, the pouch containing slightly moist powder can release nicotine (or its salt) and other flavoring agents in a continuous time period. The use of PG or any other type of wetting agent mentioned above can also advantageously help prevent material from being released unexpectedly from the pouch, for example, by agglomerating the finer parts of the powder, which otherwise may be able to pass through the holes in the pouch film.
[0096] Slightly moist powders generally have the form of a dough or paste.Such slightly moist powders can be prepared by simply mixing liquid or low melting point components with the dry powder of the present invention.
[0097] The oral preparations of the present invention may also contain one or more preservatives. Substances that may be used as preservatives include sodium benzoate and potassium sorbate and other substances with similar functions known in the art. Preservatives may be particularly suitable for slightly moist oral preparations, such as those containing glycerin and / or propylene glycol.
[0098] The composition of the present invention also provides stable storage of nicotine (or its salt) before use. The composition of the present invention (or oral preparation) is preferably stored in an airtight container, such as a can or a bag, before use, and it can be stored in this way for weeks or months without the significant loss of nicotine and without the significant degradation of the release curve. Suitable storage containers are known to those skilled in the art and include any conventional closable container. These storage containers can provide a convenient and portable system that can accommodate powder or one or more pouches. Therefore, another aspect of the present invention relates to a closable container, which includes a powder of the present invention, such as at least 1g or more of the powder. Therefore, another aspect of the present invention relates to a closable container, which includes one or more and preferably multiple oral preparations of the present invention (such as nicotine pouches).
[0099] The powder composition of the present invention is capable of both immediate and sustained release, but is particularly suitable for products intended for slow and / or sustained release (eg, intraoral preparations).
[0100] An intraoral formulation capable of providing sustained release of nicotine allows the user to obtain a long-lasting sensory experience using a minimal amount of formulation per day. This feature improves patient compliance and minimizes disruption to an individual's lifestyle when the formulation is intended for use as part of a therapeutic approach to treat nicotine dependence.
[0101] The term "sustained release" is used herein synonymously with the term "controlled release" and will be understood by the skilled artisan to include formulations that provide and / or are adapted to provide "sustained", "delayed" and / or "extended" release of nicotine (wherein the nicotine is released at a sufficiently delayed rate to produce a therapeutic response or provide a pleasurable experience over an extended period of time compared to pouch formulations currently on the market).
[0102] The powder compositions of the present invention (and oral formulations containing these powder compositions) can achieve an almost constant release rate in intervals of about 10 minutes to about 1 hour, possibly longer. In one embodiment, the compositions and formulations can achieve an almost constant release rate in intervals of about 10 to 30 minutes. This means that the release of nicotine from the product occurs continuously (at a non-zero rate) within a specified time interval. Constant release can be further defined as a composition or formulation that can maintain a steady-state concentration in a body fluid with a deviation from the mean value of no more than about 20% (e.g., about 10%) during a dosage interval.
[0103] When kept in the mouth, the powder of the present invention is advantageously able to release a high proportion of the material held in the hole. By this, we mean that when the powder is kept in the mouth for an extended period of time (e.g., at least 10 minutes or preferably at least 20 minutes), at least 75% (e.g., at least 80%, at least 85%, or at least 90%) of the nicotine stored in the pores of the chemically bonded ceramic system is released from the pores and available to the user. This feature of near-complete release allows the user to know more accurately how much nicotine is taken into the body, which may be advantageous when administering to the patient for therapeutic purposes. When the powder of the present invention is used in a nicotine pouch (such as those described herein), once nicotine (or its salt) is released from the pores of the chemically bonded ceramic system, it can immediately escape the pouch and be absorbed by the user.
[0104] In addition, powder of the present invention can realize substantially complete release within a time range suitable for therapeutic use. As demonstrated in the examples, when kept in the mouth, powder of the present invention can release nearly all releasable nicotine in about 20 minutes. The user of nicotine pouch usually keeps a single pouch in their mouth for a time period of five minutes to an hour, while releasing nicotine, wherein 20 to 30 minutes is the most common time range. This feature helps to minimize the waste of unused nicotine when the product has been consumed, and makes the powder of the present invention and the pouch containing the powder particularly suitable for therapeutic treatment, such as nicotine replacement therapy or helping to quit smoking.
[0105] The total amount of nicotine delivered by each oral preparation is preferably from about 0.5 mg to about 15 mg, for example from about 1 mg to about 10 mg. For example, the preparation can deliver from about 1 mg to about 8 mg, from about 1.5 mg to about 7.5 mg, from about 2 mg to about 5 mg, from about 2.5 mg to about 5 mg, from about 3 to about 10 mg, from about 3 to about 7.5 mg or from about 3 mg to about 5 mg. In a further example, the oral preparation can contain about 1.5 mg, about 2 mg, about 2.5 mg, about 3 mg, about 3.5 mg, about 4 mg, about 5 mg or about 6 mg calculated by free nicotine base. In particular, the amount of nicotine is 2 mg, 3 mg, 4 mg or 6 mg. The above values refer to the amount of nicotine in the form of free alkali that can be delivered from each oral preparation, whether nicotine is provided in free alkali, salt or any other form.
[0106] The powder of the present invention is suitable for use in a conventional sized nicotine pouch which is intended to be used by holding the pouch under the lips in the mouth. Typically, such a pouch is rectangular and has a length of about 25 to about 35 mm and a width of about 10 to about 15 mm.
[0107] The powder of the present invention can also provide nicotine in a relatively concentrated form, so that it is possible to manufacture a pouch that still contains a conventional amount of nicotine and has a favorable release characteristic as described herein. The powder of the present invention can contain at least 50 mg (such as at least 60 mg, at least 70 mg or at least 80 mg) of nicotine per gram of powder (calculated as free base, regardless of its presence). For example, 12 mg of nicotine (calculated as free base) can be incorporated into a chemically bonded ceramic system to obtain a powder with a total mass of no more than 0.15 g. In this article, the pouch can have a size of no more than 20 mm, preferably a size of no more than 15 mm. Typically, the pouch is rectangular and has a length of about 10 to about 15 mm and a width of about 8 to about 10 mm.
[0108] The amount of nicotine contained in the oral formulation prior to use may exceed the amount of nicotine intended to be delivered to the user. This is because a certain proportion of the nicotine may be trapped in the chemically bonded ceramic system in a manner that makes it impossible to fully release the nicotine within the possible period of use. However, preferably, the oral formulation is capable of releasing substantially all of the nicotine or a salt thereof when in contact with an aqueous liquid (e.g., saliva). By this, we mean that the oral formulation is capable of releasing at least 80% by weight (e.g., at least 90% by weight) of nicotine or a salt thereof when in contact with an aqueous liquid.
[0109] Specific powder compositions that may be mentioned include compositions comprising:
[0110] a solid porous chemically bonded ceramic system formed from a material selected from the group consisting of alpha-tricalcium phosphate, tetracalcium phosphate, calcium sulfate, and combinations thereof;
[0111] Nicotine or its salts; and
[0112] optionally a substance selected from the group consisting of glycerol, propylene glycol, polyethylene glycol (PEG) and sodium alginate, preferably in an amount of 0.1 to 10% by weight of the powder;
[0113] For example wherein the chemically bonded ceramic system is formed in the absence of a pH modifier. The powder composition may advantageously be contained within a nicotine pouch.
[0114] Medical and recreational use
[0115] The powders of the present invention have medicinal and / or recreational uses.
[0116] The powder can be placed in the mouth and then moistened by contact with saliva. For example, the powder can be provided in the form of a pouch (or other intraoral preparation), placed in the mouth, contacted with lips, gums or cheeks, and left there for a prolonged period of time. Typically, the intraoral preparation is retained in the mouth for a period of five minutes to one hour. If the intraoral preparation is customized to provide a slower sustained release of nicotine, for example, by including a controlled release agent such as hydroxypropyl methylcellulose, a longer duration is possible.
[0117] In the medical context, the powder of the present invention can be used to treat nicotine dependence (e.g., nicotine addiction), to help individuals reduce smoking or completely stop smoking. Therefore, the powder of the present invention can be described as being useful for helping to quit smoking. The powder of the present invention has several benefits that make it particularly suitable for helping to quit smoking. First, they can release almost all of the nicotine stored in the hole, and this in turn allows the user or clinician to accurately know how much nicotine has been applied to the patient. Secondly, the powder provides substantially complete release within a time range suitable for therapeutic use, such as within 20 minutes or within 30 minutes. This time range is consistent with the amount of time that a commercially available nicotine pouch is usually kept in the mouth when in use. The waste of nicotine is also minimized, because once the product is used, there is almost no unused nicotine.
[0118] In another aspect of the present invention, a method for treating nicotine dependence (e.g., nicotine addiction) is provided, wherein the method comprises applying powder of the present invention to a person suffering from nicotine dependence symptoms. Similarly, powder of the present invention can be used to treat (e.g., alleviate) one or more symptoms of nicotine dependence (including nicotine addiction or nicotine withdrawal) or help quit smoking. Such symptoms may include craving for nicotine, anger / irritability, anxiety, depression, impatience, difficulty sleeping, restlessness, hunger or weight gain and / or difficulty concentrating. Described purposes may also be referred to as nicotine replacement therapy.
[0119] Nicotine can also be used to improve symptoms associated with various diseases, including dementia, Alzheimer's disease, Parkinson's disease, Huntington's disease and depression. Therefore, in another aspect of the present invention, a method for improving symptoms associated with dementia, Alzheimer's disease, Parkinson's disease, Huntington's disease and depression is provided, wherein the method comprises administering the preparation of the present invention to a person suffering from the symptoms.
[0120] For the avoidance of doubt, "treatment" includes therapeutic treatment of a condition, as well as symptomatic treatment, prophylaxis or diagnosis.
[0121] The compositions and oral formulations of the present invention are capable of releasing a pharmacologically effective amount of nicotine during normal use. A "pharmacologically effective amount" refers to the amount of nicotine that can impart the desired therapeutic effect to the treated patient, whether administered alone or in combination with another active ingredient. This effect can be objective (i.e., measurable by some test or marker) or subjective (i.e., the subject gives an indication of the effect or feels the effect).
[0122] More preferred oral formulations of the invention may be adapted (eg, as described herein) to provide a sufficient dose of nicotine within a dosing interval (regardless of the number of doses per unit time) to produce a desired therapeutic effect.
[0123] Therefore, the amount of active ingredients that can be used in the oral formulations of the present invention can be determined by the standard of care, physician or technician according to the most suitable individual patient or condition to be treated. This may vary with the type and severity of the condition to be treated, as well as the age, weight, sex, renal function, liver function and response of the specific patient to be treated.
[0124] A suitable daily dose of nicotine for medical and recreational purposes may be from about 1 to about 100 mg / day. Conventional cigarettes typically contain between about 8 and 15 mg of nicotine. In one embodiment, each nicotine pouch of the present invention is capable of delivering about 3 to about 15 mg of nicotine. Preferably, the product disclosed herein is capable of delivering at least as much nicotine as one cigarette.
[0125] The above dosages are illustrative of the general case; there can, of course, be individual instances where higher or lower dosage ranges are warranted, and such are within the scope of this invention.
[0126] The entry of moisture into the pores of the chemically bonded ceramic system causes the release of nicotine (or its salt) contained therein. When the alkalinity of the oral environment at the absorption site in the mouth increases, the rate and extent of nicotine absorption into the body through the oral mucosa increases, and the use of a chemically bonded ceramic carrier that acts as a source of alkalinity or the inclusion of a pH adjuster in the formulation promotes this. In an embodiment of the present invention, at least 50% by weight of the nicotine released from the intraoral formulation is absorbed through the oral mucosa.
[0127] Nicotine may be delivered along with sweeteners and / or other flavorings that help mask the taste of the nicotine while ensuring that the intended benefits resulting from the absorption of nicotine are still achieved.
[0128] When used for recreational purposes, powders and intraoral formulations are capable of delivering sufficient amounts of nicotine to provide the user with a pleasurable sensory experience.
[0129] The powders and intraoral formulations of the present invention can also improve the oral health of the user. As discussed above, this is particularly true for powders and intraoral formulations in which the chemically bonded ceramic system contains calcium and is capable of releasing this mineral (e.g., in the form of dissolved calcium ions) into the saliva and optionally also increasing the pH of the saliva in and near the product in use by releasing hydroxide ions. The dissolved calcium aids in the remineralization of teeth and bones and can therefore promote mineral growth on the surface of the teeth. This type of intraoral formulation has potential use in repairing tooth enamel and strengthening teeth.
[0130] The powders and oral formulations of the present invention may have the following advantages: they provide an extended release of nicotine (e.g., nicotine is released at a sufficiently delayed rate to produce a therapeutic response or give a pleasurable experience over an extended period of time compared to pouch formulations currently on the market). The powders and oral formulations of the present invention may also have the following advantages: they may be more effective, less toxic, more rapid in action, more potent, produce fewer side effects, be more easily absorbed and / or have better pharmacokinetic characteristics, have higher bioavailability and / or have other useful pharmacological, physical or chemical properties than pharmaceutical compositions known in the prior art.
[0131] Use of the chemically bonded ceramic systems described herein can provide products that provide acceptable levels of nicotine release when placed in the mouth while minimizing the risk of exposure to the nicotine (or its salts) stored therein, such as through leakage.
[0132] Chemically bonded ceramic systems are also easy to manufacture, without the need for high temperature sintering, and therefore additional elements such as flavorings, fillers, etc. can be incorporated into the carrier to help achieve the desired sensory experience. The ability to incorporate nicotine (or its salt) into the carrier when forming the network structure also allows for better control over the amount of nicotine ultimately delivered to the user.
[0133] When the word "about" is used herein in the context of dimensions (e.g., values, temperatures, pressures (applied forces), relative humidity, size and weight, particle or grain size, pore size, time range, etc.), amounts (e.g., relative amounts (e.g., number or percentage) of particles, individual ingredients in a composition or component of a composition, and absolute amounts, such as a dose of nicotine, number of particles, etc.), deviations (from a constant, degree of degradation, etc.), it is understood that these variables are approximate and therefore may vary by ±10%, e.g., ±5%, and preferably ±2% (e.g., ±1%) relative to the numerical values specified herein. BRIEF DESCRIPTION OF THE DRAWINGS
[0134] The present invention is illustrated by the following examples, in which:
[0135] Figure 1Release profiles of nicotine-loaded powders prepared in the presence (triangles) and absence (circles) of sodium bicarbonate are shown;
[0136] Figure 2 The effect of different drying conditions and the presence or absence of sodium bicarbonate on the amount of nicotine that can be released from a molded tablet is shown;
[0137] Figure 3a and 3b Shows the storage Nicotine release profiles of powdered mixtures with particle sizes ranging from 100 μm to 200 μm in sachets and commercial Nicotine release profile of Mini Dry (particle size 100 μm to 200 μm) with two time scales;
[0138] Figure 4a and 4b The nicotine release of three powdered mixtures according to the invention is shown ( Figure 4a ) and pH measurement ( Figure 4b );
[0139] Figure 5a and 5b The nicotine release of the slightly moist pouch of the present invention (containing propylene glycol) and the dry pouch of the present invention ( Figure 5a ) and pH measurement ( Figure 5b );
[0140] Figures 6a to 6d The nicotine release and pH results of the dry formulation of the present invention, the dry commercial product and the slightly moist commercial product after storage at 33% or 60% RH for up to 34 days are shown;
[0141] Figure 7 Release profiles of nicotine-loaded alkaline bioceramics are shown;
[0142] Figure 8 The pH profile of the nicotine-loaded alkaline bioceramic is shown;
[0143] Fig. 9 shows the nicotine release profile of a mixture of an alkaline bioceramic pH modifier and nicotine-loaded calcium sulfate;
[0144] Fig.10 shows the pH profile of a mixture of an alkaline bioceramic pH modifier and nicotine-loaded calcium sulfate;
[0145] Fig.11 The release profile of nicotine-loaded alkaline bioceramics compared with commercial products is shown;
[0146] Fig.12The pH profile of the nicotine-loaded alkaline bioceramic compared to the commercial product is shown;
[0147] Fig.13 The dissolution of nicotine (by weight) from calcium sulfate bioceramics loaded with different amounts of nicotine over time is shown;
[0148] Fig.14 The dissolution of nicotine (in percentage) over time from calcium sulfate bioceramics loaded with different amounts of nicotine is shown;
[0149] Fig.15 Shown is the percentage of nicotine released from various products during a 20-minute usage period. DETAILED DESCRIPTION
[0150] Examples
[0151] Example 1 - Effect of Sodium Bicarbonate and Sodium Carbonate on Nicotine During Loading
[0152] Material
[0153] The nicotine salt used is USP grade nicotine bitartrate dihydrate. The pH adjuster used is standard food grade sodium bicarbonate (herein referred to as E500). BP and DAB grade calcium sulfate hemihydrate is used to form a chemically bonded ceramic system.
[0154] method
[0155] (i) No E500:
[0156] use 12.4954 g of BP, DAB grade calcium sulfate hemihydrate and 0.5252 g of nicotine bitartrate dihydrate were dry mixed in a mixer at 46 rpm for 10 minutes. As a next step, 10.0 g of water was added and a paste was formed by manual mixing using a spatula. The paste was cast into rectangular plates of approximately 11 x 13 cm and 2 mm thick. The plates were hardened at 35° C. and about 95% humidity for about 1 hour, and the hardened paste was then dried at room temperature for about 18 hours, then crushed and sieved. The dried plates were manually crushed using a spoon, pestle and mortar, and the mixture was sieved using a sieve. The AS200Basic vibrating screen set was used for sieving to obtain a particle size fraction in the range of 100 μm to 500 μm.
[0157] (ii) With E500:
[0158] 0.5258 g of nicotine bitartrate dihydrate and 0.5249 g of E500 were mixed with 10 mL of water. As a next step, the liquid was added to 12.5064 g of calcium sulfate hemihydrate BP, DAB grade, and a paste was formed by manual mixing using a spatula. The paste was cast into rectangular plates of approximately 11 x 13 cm and 2 mm thick. The plates were left to harden overnight at 30°C and about 95% humidity, and the hardened paste was then left to dry at room temperature for about 18 hours before being crushed and sieved. The dried plates were crushed manually using a spoon, pestle and mortar, and the mixture was sieved using a sieve. AS200Basic vibrating screen group was used for sieving to obtain particle size fractions.
[0159] analyze
[0160] All the crushed powder is put into commercially available "snuff" pouches for home snuff making. The pouches are made of non-woven cellulose and can be welded with mild heat.
[0161] Extraction experiments were performed using a dissolution test set up according to USP 711 Apparatus 2 with a small vessel. Briefly, the sample was placed in 100 ml of phosphate buffer pH 6.8 at 37°C with a stirring paddle at 50 rpm. 1 ml samples were then taken out at different time points for analysis. The amount of dissolved nicotine was determined using an HPLC system.
[0162] Results and Conclusions
[0163] In the absence of E500 during the preparation of the paste, the extractable amount of nicotine present in the powder was 70% of the amount of nicotine loaded. When E500 was present during loading, the extractable amount of nicotine present in the powder was 25%-30% of the amount of nicotine loaded. The results are shown in Figure 1 middle.
[0164] The addition of sodium bicarbonate during the manufacture of the paste significantly reduces the amount of nicotine that can be extracted from the sample.
[0165] A similar experiment was also conducted in which a pulverized powder was produced according to the above method (i) and then mixed with sodium bicarbonate in an amount corresponding to the amount used in method (ii). This mixture was also placed in a "snuff" pouch. The analysis of nicotine release was assessed using the above method, and it was found that the release profile was consistent with that observed for a powder manufactured by method (i) and not subsequently mixed with sodium bicarbonate. This confirms that sodium bicarbonate only affects the nicotine release profile of the final powder when sodium bicarbonate is present during the step of hardening the aqueous calcium sulfate hemihydrate paste.
[0166] Further similar experiments were also conducted using sodium carbonate instead of sodium bicarbonate. The results of these experiments showed that the addition of sodium carbonate to a mixture containing water, nicotine bitartrate dihydrate and calcium sulfate hemihydrate also reduced the nicotine content of the finished powder.
[0167] Example 2
[0168] This experiment was conducted to further explore the mechanism behind the nicotine loss observed in Example 1.
[0169] method
[0170] Samples formed using nicotine in the form of BP and DAB grade calcium sulfate hemihydrate and USP grade nicotine bitartrate dihydrate were prepared according to the method described in Example 1. Half of the samples contained sodium bicarbonate and the other half did not.
[0171] In contrast to Example 1, the paste was moulded into tablets using empty tablet blisters and then hardened under different conditions as described below (instead of casting the crushed and sieved plaques).
[0172] Two sets of hardening conditions were used:
[0173] "Zip": Store the molded paste at room temperature to 24°C in an airtight zipper bag not much larger than a blister.
[0174] 100% RH: Plates were stored at approximately 100% relative humidity and 30°C for a period of time and then "dried" at room temperature prior to analysis.
[0175] analyze
[0176] The analysis was performed by extracting the molded tablets. Each tablet was placed in a 50 mL Falcon tube containing 15 mL of distilled water. The tube was placed on a shaker for about 1 hour, and then the extract was analyzed at a wavelength of 260 nm using a UV-spectrophotometer system (VWR UV-3100PC). A standard curve was obtained using a prescribed solution containing nicotine base.
[0177] result
[0178] Figure 2 The results are shown in . Adding sodium bicarbonate (E500) to the formulation during the manufacture of the paste significantly reduced the amount of extractable nicotine. Allowing the material to solidify and harden in a slightly humid and warm environment significantly reduced the amount of extractable nicotine.
[0179] The results suggest that the addition of pH adjusters should be performed by mixing the dry components or otherwise incorporated into the formulation after hardening, crushing and sieving of the chemically bonded ceramic system.
[0180] Example 3 – Comparison with commercial products
[0181] method
[0182] Samples formed using nicotine in the form of BP and DAB grade calcium sulfate hemihydrate and USP grade nicotine bitartrate dihydrate were prepared and analyzed according to the method described in Example 1. The dried plates were manually crushed using a spoon, pestle and mortar and pounded using AS200Basic vibrating screen set is used to sieve to obtain particle size fractions. In this example, only the 100 μm to 200 μm size fraction is used. The particles are placed in an empty and clean The pouch is then resealed using heat.
[0183] The commercial product tested was a dried, well-known Swedish product purchased in convenience stores. Mini Dry. For The product was cut open and the powder inside was taken out and sieved as in the above example. The fraction of 100 μm to 200 μm was selected and put back into the pouch and sealed.
[0184] Analysis of nicotine release was performed as described in Example 1.
[0185] result
[0186] For commercial use Incorporating nicotine into a chemically bonded ceramic system formed from calcium sulfate showed the same level of nicotine release as the Mini Dry product, but the release time was prolonged. Figure 3a and 3b For comparison reasons, the scale on the Y-axis was normalized, meaning that for each curve the amount extracted at the last measured time point was set to 100%.
[0187] Example 4 - pH comparison with commercial products
[0188] method
[0189] Samples were prepared using nicotine in the form of BP and DAB grade calcium sulfate hemihydrate (CaSH), USP grade nicotine bitartrate dihydrate as follows:
[0190] 23.1186 g of CaSH were weighed on an Al foil. 2.4886 g of nicotine bitartrate dihydrate was dissolved in 10 g of distilled water in a beaker. The nicotine-water solution was added to the powder and the beaker was rinsed with 8 g of distilled water added to the mixture. The mixture was stirred by hand for about 1 minute and then spread evenly on the sheet. The material was left to dry at room temperature for 48 hours. Thereafter, the material was crushed using a pestle and mortar and finally pulverized using The AS 200 Basic vibrating screen set was used for sieving to obtain particles ranging from 50 μm to 500 μm. The powder was tested using a spectrophotometer to confirm the nicotine content.
[0191] 300 mg of the resulting powder was mixed with 3.62 wt% of Ph. Eur grade anhydrous sodium carbonate and sealed in a pouch made of non-woven cellulose. The pH produced by the pouch in distilled water was then measured and compared with seven different commercial products (Nils Cortado, Cool Mint Slim, Spearmint Breeze, Berry, Nordic Elderflower, Ice Cool and The pH was compared with that obtained with Cool Mint Mini Dry.
[0192] analyze
[0193] Nicotine Analysis:
[0194] 300 mg of the powder was diluted in 100 mL of distilled water and shaken for about 1 minute. The dilution was then analyzed in a UV-spectrophotometer system (VWR UV-3100PC) at a wavelength of 260 nm.
[0195] pH analysis:
[0196] pH was measured using a calibrated Mettler Seven Compact pH / Ion S220 System with Mettler InLab Expert Pro Electrode. Place each pouch in a beaker with 25 mL of distilled water and stir for 30 minutes using a magnet and magnetic stirrer. After 30 minutes, remove the magnet and pouch and measure the pH.
[0197] result
[0198] Nicotine Analysis:
[0199] 100% of added nicotine was recovered in the samples
[0200] pH analysis:
[0201] The pH results are summarized in Table 1 below.
[0202] Table 1 – pH results
[0203]
[0204] Nils Cortado contains bamboo fiber and microcrystalline cellulose (MCC) as fillers. Cool Mint Slim uses MCC and plant fiber as fillers. MCC was used as a filler. Use MCC and maltitol as bulking agents. Nordic Use Poliacrilex, which is a gum base that contains nicotine. MCC was used as a filler.
[0205] It can be concluded that the pH of the chemically bonded ceramic system is consistent with the commercial product.
[0206] Example 5 - Loaded Powder for Nicotine Pouches
[0207] Representative oral formulations containing nicotine-loaded powders prepared according to the methods of the present invention are illustrated below.
[0208] Table 2 - Oral Preparations
[0209] Element Quantity (%w / w) Nicotine-loaded base powder 91.9 Sucralose 0.1 Sodium carbonate 3.2 Sodium chloride 1.8 NP Ice Cool(flavor) 3.0
[0210] method
[0211] Nicotine loaded base powders were prepared using nicotine in the form of BP and DAB grade calcium sulfate hemihydrate (CaSH) and USP grade nicotine bitartrate dihydrate as follows:
[0212] 170.4 g of nicotine tartrate was dissolved in 1215.7 g of deionized water in a household blender. 1519.6 g of CaSH was added in batches. The mixture was stirred for about 3 minutes on a blender using medium speed. Thereafter, the blend was poured onto a silicon canvas with metal walls and allowed to stand to form a plate about 10 mm thick. The plate was then placed on a perforated metal plate and dried at room temperature for about 24 hours. The cast plate was then broken into smaller pieces using a pestle and mortar and finally ground in a household flour mill. The mixture was then ground using The resulting powder was sieved using an AS200Basic vibrating screen set to obtain particles in the range of 50 μm to 500 μm. The resulting powder ("nicotine-loaded base powder") was then mixed with the remaining components according to Table 2 above. The components were weighed into a covered glass vessel and sieved on a WAB plate. The mixture was mixed in a mixer at 60 rpm for 1 hour. After mixing, a portion of the powder mixture was filled and sealed in three separate non-woven bags using a bag making machine. Approximately 0.3 g of powder was filled in each bag.
[0213] analyze
[0214] Suspend the pouch in a wire "cage" in a beaker filled with 50 mL of deionized water. Add a magnet to the beaker and immediately place it on a magnetic stirrer.
[0215] pH
[0216] pH was measured using a calibrated Mettler Seven Compact pH / Ion S220 System with Mettler InLab Expert Pro electrode. The pH meter was set to automatic measurement and the pH was measured every minute.
[0217] Nicotine Release
[0218] The samples were manually taken out using a pipette and then analyzed using a UV-spectrophotometer (VWR UV-3100PC) at a wavelength of 260 nm.A standard curve was obtained using a defined solution containing nicotine base.
[0219] result
[0220] For each of the three pouches, Figure 4a and 4b The resulting curves from nicotine release and pH measurements are seen in .
[0221] Example 6 - Slightly Moist Nicotine Pouch
[0222] A slightly moist formulation was produced by mixing the powder formulation from Example 5 with 17 wt% propylene glycol (PG). 0.6 g of the powder from Example 5 was mixed with 0.1 g of PG in a beaker using a spatula. The resulting mixture had a texture and consistency similar to that of the commercial slightly moist product.
[0223] analyze
[0224] Nicotine release and pH were tested according to the method of Example 5.
[0225] result
[0226] The results of nicotine release and pH are shown in Figure 5a and 5b , where the "slightly moist" formulation was compared to the dry formulation of Example 5. The data showed that the nicotine release rate was comparable for both the dry formulation and the slightly moist formulation, demonstrating that both the dry formulation and the slightly moist formulation were able to provide sustained release of nicotine over a meaningful time frame.
[0227] Example 7 – Taste Evaluation
[0228] A small-scale subjective evaluation was conducted on nicotine pouch users (n=4). Each user was provided with a canister having a pouch produced according to Example 5, having two different flavors, one citrus and one mint (Powder 1 and Powder 2), as follows:
[0229]
[0230] Each subject also received one dry and one slightly moist can of a mint-flavored commercial competitor product ( Mini dry and Slim) for comparison. Subjects were asked to rate the smell of the can, how quickly the nicotine takes effect, how long the nicotine is released, how quickly the flavor takes effect, and how long the flavor is released.
[0231] Results are given based on comparison with dry and slightly moist commercial products
[0232] 1. The smell when opening the can:
[0233] Powders 1 and 2 had better and stronger smells compared to the commercial dry product and were similar to the commercial slightly moist product.
[0234] 2. Nicotine takes effect:
[0235] The commercial slightly moist product had the fastest nicotine onset. Powders 1 and 2 were equal to or faster than the commercial dry product.
[0236] 3. Duration of nicotine release:
[0237] Powders 1 and 2 had a much longer nicotine release than the commercial dry product and a longer nicotine release than the commercial slightly moist product.
[0238] 4. Flavor effect:
[0239] The flavor of powders 1 and 2 was perceptible and fully developed more quickly than the commercial dry product. The performance of the commercial slightly moist product was intermediate between the dry commercial product and powders 1 and 2.
[0240] 5. Flavor duration
[0241] The flavor release duration of powders 1 and 2 was much longer than both the dry and slightly moist commercial products. The slightly moist commercial product had a longer flavor duration than the dry product. Powders 1 and 2 released flavor long after the nicotine was released, at least 45 to 60 minutes. One subject even kept a pouch with powder 1 in his mouth for up to three hours and still had good flavor from the pouch. The dry commercial product typically lost all flavor within 10 minutes, while the slightly moist commercial product lost all flavor within 15 to 20 minutes.
[0242] Example 8 - Storage Stability
[0243] The following method was used to determine the stability of the formulations of the present invention under humid conditions.
[0244] Test Materials
[0245] The test formulation of the present invention (referred to as "bioceramic powder") was prepared according to the method in Example 5. A commercial dry formulation and a slightly moist formulation were used for comparison. The formulation was provided in powder form for storage, which was then sealed in a pouch made of non-woven cellulose before storage.
[0246] Storage conditions
[0247] Store sealed sachets under the following conditions:
[0248] Test duration: 34 days.
[0249] Utensils / Containers: In open pouch jars without lids. Place jars in larger sealed plastic containers with varying humidity levels.
[0250] Temperature: Room temperature. Usually varies between 20°C and 23°C.
[0251] Humidity: Two different levels of relative humidity ("RH") were used: 33% and 60% RH. RH was controlled by saturating saline solutions with different salts in the bottom of a plastic container as described in Greenspan L., Journal of Research of the National Bureau of Standards, Vol. 81A, No. 1, 1977, 89-96.
[0252] analyze
[0253] Nicotine content before and after storage was analyzed using UV-spectrophotometry as in Example 5. pH measurements were performed using the method in Example 5.
[0254] result:
[0255] For 33% and 60% RH, nicotine release and pH results are shown in Figures 6a to 6d In these figures, "bioceramic powder" refers to the test results of the pouches containing the test formulation of the present invention. The results show that after 4 weeks of storage, the nicotine releasable from the nicotine pouches containing the formulation of the present invention is higher. This shows that the formulation of the present invention has storage stability properties that are as good as the dry commercial product (in terms of nicotine release under the test conditions) and better than the storage stability properties of the slightly moist commercial product.
[0256] Example 9 – Alkaline bioceramics as carriers and pH regulators
[0257] Material
[0258] Nicotine Bitartrate Dihydrate USP Grade
[0259] Deionized water
[0260] (CS) Calcium silicate powder (CaO / SiO2=1 / 1)
[0261] (PC) Portland Cement
[0262] (TTCP) Tetracalcium Phosphate
[0263] method
[0264] Nicotine bitartrate dihydrate was dissolved in deionized water to obtain a solution with a nicotine concentration of 60 mg / ml.
[0265] 1 g of CS was weighed into a beaker. 0.4 ml of nicotine solution was added and the mixture was stirred with a spatula for 1 minute. The mixture was left for 5 minutes and then transferred to aluminum foil and "dried" at room temperature for 1 hour. Thereafter, the hardened cement was crushed using a pestle and mortar. 0.3 g of the resulting powder was placed in a standard-sized pouch made of nonwoven material for analysis.
[0266] For the Portland cement products, the samples were produced using exactly the same method as for CS, using PC instead of CS.
[0267] The TTCP product was prepared using the same method as the CS product, except that the w / c (water: cement) ratio was changed from 0.4 to 0.6. Thus, the nicotine solution was diluted with more deionized water to obtain the same amount of nicotine in the mixed cement.
[0268] analyze
[0269] Suspend the pouch in a wire "cage" in a beaker filled with 50 mL of deionized water. Add a magnet to the beaker and immediately place it on a magnetic stirrer.
[0270] pH
[0271] pH was measured using a calibrated Mettler The pH was measured using a Seven Compact pH / Ion S220 system equipped with a Mettler Toledo InLab Expert Pro electrode. The pH meter was set to automatic measurement and the pH was measured every minute.
[0272] Nicotine Release
[0273] The samples were manually taken out using a pipette and then analyzed using a UV-spectrophotometer (VWR UV-3100PC) at a wavelength of 260 nm.A standard curve was obtained using a defined solution containing nicotine base.
[0274] result
[0275] For each of the three powders, Figure 7 and 8 The resulting curves from nicotine release and pH measurements are seen in .
[0276] Example 10 - Different carriers and pH adjusters
[0277] This example illustrates the use of calcium silicate, Portland cement and sodium carbonate as pH adjusters added to a calcium sulfate based nicotine powder.
[0278] Material
[0279] Nicotine Bitartrate Dihydrate USP Grade
[0280] Deionized water
[0281] (CSH)BP, DAB grade calcium sulfate hemihydrate
[0282] (CS) Calcium silicate powder (CaO / SiO2=1 / 1)
[0283] (PC) Portland Cement
[0284] (SC)Sodium carbonate
[0285] method
[0286] Nicotine loaded base powders were prepared using nicotine in the form of BP and DAB grade calcium sulfate hemihydrate (CaSH) and USP grade nicotine bitartrate dihydrate as follows:
[0287] 170.4 g of nicotine tartrate was dissolved in 1215.7 g of deionized water in a household blender. 1519.6 g of CaSH was added in batches. The mixture was stirred for about 3 minutes on a blender using medium speed. Thereafter, the blend was poured onto a silicon canvas with metal walls and allowed to stand to form a plate about 10 mm thick. The plate was then placed on a perforated metal plate and dried at room temperature for about 24 hours. The cast plate was then broken into smaller pieces using a pestle and mortar and finally ground in a household flour mill. The mixture was then ground using The resulting powder was sieved using an AS200Basic vibrating screen set to obtain particles in the range of 50 μm to 500 μm. The resulting powder (“nicotine-loaded base powder”) was then mixed with CS and PC, respectively, to produce two different powders. In addition, a powder was prepared in which the alkaline agent used was the standard reagent sodium carbonate, powder 3.
[0288] Powder 1: 1 g of nicotine-loaded base powder mixed with 5 wt% CS
[0289] Powder 2: 1g of nicotine-loaded base powder mixed with 3.5wt% PC
[0290] Powder 3: 1 g of nicotine-loaded base powder mixed with 3.5 wt% SC
[0291] The powders were mixed manually in a beaker using a spatula to produce a homogeneous blend. 0.3 g of the resulting powders were individually placed in standard sized pouches made of non-woven material for analysis.
[0292] analyze
[0293] pH and nicotine release were performed according to the method described in Example 9.
[0294] result
[0295] The resulting nicotine release and pH profiles can be respectively Fig. 9 and 10 Seen in.
[0296] Example 11 – Comparison of Nicotine Release and pH Profiles
[0297] The pH development and nicotine release of the powder from Example 9 were compared with the commercial product The pH development of Mini Dry was compared.
[0298] method
[0299] Sachets with 0.3 g of powders 1, 2 and 3 from Example 9 were prepared using the same method as Example 9. Commercial products were used directly from their commercial packaging.
[0300] analyze
[0301] The same method as in Example 9 was used for pH analysis and nicotine release.
[0302] result
[0303] The results can be found in Fig.11 and 12 Seen in.
[0304] Example 12 - Slightly Moist Formulation
[0305] Made of texture, consistency and moisture content similar to commercially available slightly moist ( Slim) product.
[0306] The powder from Example 9 was mixed with 10%, 15% and 20% by weight of propylene glycol (PG) in a beaker using a spatula. The resulting mixtures all had a texture, consistency and wetness comparable to commercially available slightly moist products, although there were differences in wetness and adhesion between them. A pouch with 0.3 g of each mixture was prepared using nonwoven fabric.
[0307] analyze
[0308] The same method as in Example 9 was used for pH analysis and nicotine release.
[0309] result
[0310] The pH and nicotine release are expected to be similar to the dry powder tested in Example 9.
[0311] Example 13 – User Experience Evaluation
[0312] A small-scale subjective evaluation was conducted on nicotine pouch users (n=10). Each user was provided with a canister with a pouch produced according to Example 9, which had two different flavors: one citrus and one mint. Only the CS and PC powders of Example 9 were tested, resulting in four test powders (Powders 1-4). Flavoring agents were added to the powders by hand mixing 3 wt % of the flavor liquid into the remaining components of the powder. Each subject also received a canister of dry ( Mini Dry) and a can of slightly moist ( The subjects were asked to rate the smell of the can, the speed of nicotine onset, the duration of nicotine release, the speed of flavor onset, and the duration of flavor release.
[0313] Powders 1-4 are expected to have improved or comparable performance compared to the commercial product.
[0314] Example 14 - Storage Stability
[0315] The following method was used to determine the stability of the test materials under humid conditions.
[0316] Test Materials
[0317] The powder prepared according to Example 9 was used as the test formulation. A commercial dry formulation and a slightly moist formulation were used for comparison. The formulation was provided in powder form for storage, which was then sealed in a pouch made of non-woven cellulose before storage.
[0318] Storage conditions
[0319] Store sealed sachets under the following conditions:
[0320] Duration of test: at least 4 weeks of days, optionally longer.
[0321] Utensils / Containers: In open pouch jars without lids. Place jars in larger sealed plastic containers with varying humidity levels.
[0322] Temperature: Room temperature. Usually varies between 20°C and 23°C.
[0323] Humidity: Two different levels of relative humidity ("RH") were used: 33% and 60% RH. RH was controlled by saturating saline solutions with different salts in the bottom of a plastic container as described in Greenspan L., Journal of Research of the National Bureau of Standards, Vol. 81A, No. 1, 1977, 89-96.
[0324] analyze
[0325] Nicotine content before and after storage was analyzed using UV-spectrophotometry as in Example 9. pH measurements were performed using the method in Example 9.
[0326] Example 15 – Increasing the load
[0327] Material
[0328] Nicotine Bitartrate Dihydrate USP Grade
[0329] Deionized water
[0330] (CSH)BP, DAB grade calcium sulfate hemihydrate
[0331] Sample preparation
[0332] Bioceramic powders containing different concentrations of nicotine were prepared using the following method.
[0333] Nicotine bitartrate dihydrate was dissolved in water. Calcium sulfate hemihydrate was weighed into a beaker. The water-nicotine salt solution was added to the calcium sulfate hemihydrate and manually stirred into a uniform paste. The paste was poured onto an Al foil and left for about 10 minutes. Thereafter, the solidified material was dried in a convection oven at 24 degrees Celsius for about 24 hours. Subsequently, the hardened material was manually crushed using a pestle and mortar, and the crushed material was then sieved to obtain a powder with a particle size range of 50 μm to 500 μm.
[0334] By varying the amount of nicotine salt added, three different concentrations were achieved. The nicotine concentrations measured in the powder were:
[0335] Powder 1: 10 mg nicotine per gram of powder (calculated as free base nicotine)
[0336] Powder 1: 25 mg nicotine per gram of powder (calculated as free base nicotine)
[0337] Powder 1: 83 mg nicotine per gram of powder (calculated as free base nicotine)
[0338] analyze
[0339] Before analysis, a pouch made of heat-sealable nonwoven material was manufactured in standard size. About 0.15g of powder was accurately weighed and placed in each pouch. The pouch was then sealed using a heat welder. In order to measure nicotine release, each pouch was suspended in a metal mesh cage in 100ml of distilled water in a glass beaker containing a stirrer magnet. The beaker was placed on a magnetic stirrer with a stirrer speed of 360rpm. Samples were taken out using a pipette at different time points and placed in a sealable vial for analysis. The absorbance of the analyte was subsequently measured at a wavelength of 260nm using a UV-spectrophotometer system (VWR UV-3100PC). Using a calibration curve and the known powder weight in each pouch, the absorbance of each analyte was calculated as nicotine concentration. Three samples of each nicotine concentration were measured.
[0340] result
[0341] The resulting dissolution curve is shown in Fig.13 and 14 Powders with nicotine concentrations varying between 10 and 83 mg / g can be manufactured. After 30 minutes, approximately 100% of the nicotine can be recovered in the dissolution test, and the average percentage of nicotine released after 20 minutes for all concentrations is 87%.
[0342] Example 16 - Nicotine Concentration in Nicotine Pouches Following Human Use
[0343] Pouches containing nicotine-loaded bioceramic (chemically bonded ceramic) powder were produced and compared to commercially available nicotine pouches to assess the amount of nicotine remaining after 20 minutes of human use.
[0344] Material
[0345] Nicotine Bitartrate Dihydrate USP Grade
[0346] Distilled water
[0347] (CSH)BP, DAB grade calcium sulfate hemihydrate
[0348] Manufacturing of CBC-based nicotine sachets
[0349] The manufacturing is carried out in steps, first producing chemically bonded ceramic (CBC) particles containing nicotine, mixing the resulting particles with other ingredients, and then filling the mixture into pouches.
[0350] Step 1:
[0351] 153 g of nicotine bitartrate dihydrate was dissolved in 430 ml of distilled water. 1973 g of calcium sulfate hemihydrate was weighed into the steel drum of an intensive mixer type granulator. The granulator was started at a speed of 20 m / s and the nicotine / water solution was poured in over 15 s. The granulator was run for another 15 s, then the speed was reduced to half and run for a further 120 s, then shut down and the material was checked. The granulator was turned on again at a speed of 20 m / s, an additional 100 ml of water was added, and the machine ran for 15 s and shut down. The granulator was started again, an additional 150 ml of water was added, and the granulator was run for 15 s. The resulting granules were poured onto an Al tray and dried at room temperature for 24 hours. Use The dried granules were sieved by AS200Basic vibrating screen set to obtain particles in the range of 50 μm to 200 μm.
[0352] Step 2:
[0353] The nicotine-containing CBC granules from step 1 are mixed with other ingredients to obtain a finished formulation according to Table 3. The components are mixed by dry mixing in a dry mixer.
[0354] Table 3: Components to be mixed to obtain the final nicotine formulation
[0355] Element Quantity (%w / w) Nicotine-loaded base powder 86.7 Sucralose 0.1 Sodium carbonate 6.5 Sodium chloride 1.9 NP Ice Cool(flavor) 2.8 NP Peppermint Flavor 1.0 NP Cool 1.0
[0356] After mixing, leave the powder in a closed jar for at least 24 to allow the flavor to even out.
[0357] Step 3:
[0358] The pouches of nonwoven heat-sealable material designed for use as pouches were filled with either 0.33 g or 0.15 g of the finished formulation. The pouches were sealed using a standard heat sealer. The length of the pouch containing 0.15 g was half that of the pouch containing 0.33 g, which is consistent with the commercially available The products are the same size.
[0359] The molecular structure of the chemically bonded ceramic system obtained by this method was subjected to X-ray powder diffraction analysis and was found to be identical to that obtained in Example 5. For the two hardened ceramics obtained by hydration of calcium sulfate hemihydrate, the following high intensity X-ray diffraction peaks were observed: 11.5, 20.7 and 29.2° 2θ (using a wavelength of These are also the strongest peaks observable for calcium sulfate dihydrate.
[0360] Human use testing
[0361] Two users ("User 1" and "User 2") who currently use different brands of nicotine pouches were allowed to use different nicotine pouches according to the following method. The pouches used are described in Tables 4A and 4B. Zonnic is an approved nicotine replacement therapy (NRT) product, not a product for recreational use.
[0362] Table 4A
[0363]
[0364] Table 4B – Commercial Formulations
[0365]
[0366] To test the pouch, the user places the ostomy bag between the upper lip and gums and keeps the pouch in place for twenty minutes without touching the pouch with the tongue. After twenty minutes, the pouch is removed and immediately placed in a plastic vial and frozen to -20°C pending analysis. The user tests the pouch according to Table 5. A washout period of at least 1 hour between pouch uses is mandatory.
[0367] Table 5: Number of sachets per product and user tested
[0368] Product Number 1 2 3 4 5 6 User 1 6 6 User 2 6 7 3 4
[0369] analyze
[0370] Before analysis, each used pouch was thawed at room temperature. The pouch was then suspended in a steel mesh cage in a beaker containing 100 ml of distilled water and a stirrer magnet. The assembly was immediately placed on a magnetic stirrer set at 360 rpm. After 60 minutes, the sample was taken out and analyzed at a wavelength of 260 nm using a UV-spectrophotometer system (VWR UV-3100PC) to obtain an absorbance value. Using a calibration curve based on a calibration solution of nicotine bitartrate dissolved in distilled water, the corresponding nicotine concentration can be calculated, and the amount of nicotine remaining in the pouch after use can then be calculated.
[0371] result
[0372] The results of the analysis are Fig.15 The results clearly show that the CBC pouches have significantly less nicotine remaining in the pouch after use compared to the other products.
[0373] Example 17 - Real-time stability of CBC-based nicotine pouches
[0374] The nicotine content of nicotine pouches containing the powder of the invention was measured after storage under different conditions.
[0375] Sample preparation
[0376] Three different types of samples were tested according to Table 6. They differed in the manufacturing method, storage and analysis method.
[0377] Table 6: Different samples tested
[0378]
[0379]
[0380] *The can with the sachet is kept in the user's carry-on bag and is opened from time to time
[0381] The manufacturing is carried out in steps, starting with the production of chemically bonded ceramic (CBC) powder containing nicotine, which is then mixed with other ingredients and filled into sachets.
[0382] Step 1
[0383] 42.6g USP grade nicotine bitartrate dihydrate is dissolved in 312g deionized water. 380.2g BP, Dab grade calcium sulfate hemihydrate is weighed into a bowl. Water-nicotine salt solution is added to calcium sulfate hemihydrate and manually stirred into a uniform paste. The ratio of water-nicotine salt solution and calcium sulfate hemihydrate is selected to produce a dry powder with a nicotine (free base) content of about 25-30mg per gram of powder. The paste is poured on an Al foil and placed for about 10 minutes. Thereafter, the solidified material is dried in a convection oven at 24°C for about 24 hours. Subsequently, the hardened material is manually crushed using a pestle and mortar, and the crushed material is then sieved to obtain a powder with a particle size range of 50μm to 500μm.
[0384] Step 2
[0385] The nicotine-containing CBC powder from step 1 was mixed with other ingredients to produce the finished formulation according to Table 7. The components are mixed by dry mixing in a dry mixer.
[0386] Table 7: Components mixed to obtain the final nicotine formulation.
[0387] Element Quantity (%w / w) Nicotine-loaded base powder 91.7 Sucralose 0.1 Sodium carbonate 3.3 Sodium chloride 1.9 Flavor 3
[0388] Step 3
[0389] Bagging in the lab:
[0390] A pouch of nonwoven heat sealable material designed for use as a pouch was filled with 0.3 g of powder. The pouch was sealed using a standard heat sealer.
[0391] Bagging at CMO:
[0392] The finished powder is sent to a contract manufacturing organization (CMO) to be filled into pouches using a bagging machine designed for nicotine pouch filling. The pouch material used is a non-woven heat sealable material designed for use as a pouch. Each pouch is filled with approximately 0.3 g of the final nicotine formulation.
[0393] analyze
[0394] To measure nicotine release, each pouch was suspended in a metal mesh cage in 100 ml of distilled water in a glass beaker containing a stirrer magnet. The beaker was placed on a magnetic stirrer with a stirrer speed of 360 rpm. After 30 minutes, the sample was removed using a pipette and placed in a sealable vial for analysis in a UV-spectrophotometer or HPLC system.
[0395] UV-Spectrophotometer
[0396] The absorbance of the analytes was measured at a wavelength of 260 nm using a UV-spectrophotometer system (VWR UV-3100PC). The absorbance of each analyte was calculated as nicotine concentration using the calibration curve and the known weight of powder in each pouch.
[0397] HPLC
[0398] The samples were analyzed on a Shimadzu Prominence-I LC-2030 HPLC system equipped with a UV detector.
[0399] result
[0400] The results are summarized in Table 8. The nicotine pouches had good stability over the time periods and conditions measured.
[0401] Table 8 – Stability Results
[0402]
[0403] There are some obvious sources of variability in these analyses.
[0404] Analytical methods have inherent variability.
[0405] The time period between measuring the calibration curve and measuring the samples may vary.
[0406] The weight of the CMO filled pouch is not exact. The weight is taken as the average of several pouches emptied from the same batch, but not the average of the exact pouches measured, as exact measurement requires emptying the pouch.
[0407] Nonetheless, the results indicate minimal losses in the time period and conditions studied.
[0408] Example 18 – Portland Cement Products
[0409] Hardened Portland cement is used with calcium nicotine phosphate particles as a pH adjuster.
[0410] method
[0411] Sample preparation
[0412] Step 1:
[0413] Production of calcium phosphate nicotine granules
[0414] 153 g of USP grade nicotine bitartrate dihydrate was dissolved in 430 ml of distilled water. 1973 g of DAB / BP grade calcium sulfate hemihydrate was weighed into the steel drum of an intensive mixer type granulator. The granulator was started at a speed of 20 m / s and the nicotine / water solution was poured in over 15 s. The granulator was run for another 15 s, then the speed was reduced to half and run for a further 120 s, then shut down and the material was checked. The granulator was turned on again at a speed of 20 m / s, an additional 100 ml of water was added, and the machine ran for 15 s and shut down. The granulator was started again, an additional 150 ml of water was added, and the granulator was run for 15 s. The resulting granules were poured onto an Al tray and dried at room temperature for 24 hours. Use The dried granules were sieved with an AS200 Basic vibrating sieve set to obtain particles in the range of 50 μm to 500 μm. The resulting nicotine content in the powder was approximately 6 mg nicotine / 0.3 g powder.
[0415] Step 2:
[0416] Manufacture of hardened Portland cement powder
[0417] 10 g of Portland cement and 4 g of water were manually mixed in a glass beaker to form a homogeneous paste. The paste was then placed on an Al foil at room temperature for at least 1 hour to allow it to set and harden. Thereafter, the material was manually crushed using a pestle and mortar. The AS200Basic vibrating screen set sieves the crushed powder to obtain particles in the range of 50 μm to 500 μm.
[0418] Step 3:
[0419] The hardened Portland cement is mixed with fine particles of calcium phosphate containing nicotine.
[0420] According to Table 9, 20 g of the fines from step 1 were mixed with four different amounts of hardened Portland cement powder. Mix in a dry mixer at 50 rpm for 30 minutes.
[0421] Table 9: Preparation of four powders with different wt% of hardened PC
[0422] sample Hardened PC Wt% Powder 1 1 Powder 2 2 Powder 3 3 Powder 4 5
[0423] Step 4
[0424] Fill the powder into the sachets
[0425] 0.3 g of powder was filled into a pouch of non-woven heat sealable material designed for use as a nicotine pouch. Three pouches were made for powders 2, 3 and 4 in Table 9.
[0426] analyze
[0427] Three different sets of measurements were performed on different samples, two different pH measurements and one dissolution experiment.
[0428] pH Method 1:
[0429] 0.3 g of powders 1, 2 and 4 according to Table 9 were added to 100 ml of deionized water in a glass beaker with a stirring magnet. The beaker was placed on a magnetic stirrer at 360 rpm. After 30 minutes, the pH was measured using a calibrated Mettler Toledo Seven Compact pH / Ion S220 system equipped with a Mettler Toledo InLab Expert Pro electrode. Three samples of each powder were analyzed.
[0430] pH Method 2:
[0431] Filled pouches with powders 2, 3 and 4 were suspended in a metal mesh cage in 100 ml of deionized water in a glass beaker containing a stirrer magnet. The beaker was placed on a magnetic stirrer with a stirrer speed of 360 rpm. After 30 minutes, the pH was measured using a calibrated Mettler Toledo Seven Compact pH / Ion S220 system equipped with a Mettler Toledo InLab Expert Pro electrode. Three samples of each powder were analyzed.
[0432] Dissolution:
[0433] A small bag filled with 0.3g of powder 3 according to Table 9 was suspended in a metal mesh cage in 100ml deionized water in a glass beaker containing a stirrer magnet. The beaker was placed on a magnetic stirrer with a stirrer speed of 360rpm. For dissolution analysis, a sample was taken out using a pipette after 30 minutes and placed in a sealable vial for analysis. The sample was then analyzed by measuring the absorbance at a wavelength of 260nm using a UV-spectrophotometer system (VWR UV-3100PC). The absorbance of each analyte was calculated as nicotine concentration using a calibration curve and known powder weight. Three small bags were analyzed.
[0434] result
[0435] The results of the pH measurements are presented as an average of three samples in Table 10. The desired pH of 8 or higher could be achieved with powders 3 and 4.
[0436] Table 10: Results of two different pH methods
[0437] Material pH (pH Method 1) pH (pH Method 2) Powder 1 5.4 Powder 2 7.6 7.6 Powder 3 8.1 Powder 4 10.1 8.6
[0438] The results of the dissolution experiments can be seen in Table 11. It was confirmed that at least 6 mg of nicotine was dissolved from each sample, which confirmed that the addition of hardened PC powder did not interfere with nicotine release.
[0439] Table 11: Amount of nicotine dissolved in the dissolution experiments.
[0440] pouch Dissolved nicotine (mg) 1 6.3 2 6.1 3 6.1
Claims
1. A powder comprising a solid porous chemically bonded ceramic system and nicotine or a salt thereof, wherein the nicotine or a salt thereof is located within the pores of the chemically bonded ceramic system.
2. The powder according to claim 1, wherein at least 80% by weight of the nicotine or salt thereof is located within the pores of the chemically bonded ceramic system.
3. A powder according to claim 1 or claim 2, wherein the chemically bonded ceramic system is formed in the presence of nicotine or a salt thereof.
4. Powder according to any one of the preceding claims, wherein the powder is prepared using a salt of nicotine.
5. The powder according to claim 4, wherein the salt of nicotine is nicotine tartrate, such as nicotine bitartrate dihydrate.
6. A powder according to any one of the preceding claims, wherein the powder gives a pH of at least 8 when in contact with saliva.
7. Powder according to any of the preceding claims, wherein the chemically bonded ceramic system is based on calcium phosphate, calcium sulfate, calcium silicate, calcium aluminate or mixtures thereof.
8. Powder according to any one of the preceding claims, wherein the chemically bonded ceramic system is based on calcium sulfate.
9. The powder of any one of the preceding claims, wherein the chemically bonded ceramic system is present in about 40% to about 98% by weight of the powder.
10. A powder according to any one of the preceding claims, wherein the powder further comprises a substance which is liquid at ambient conditions, or which is a low melting point solid.
11. The powder according to claim 10, wherein the substance is glycerol, propylene glycol, polyethylene glycol, sodium alginate or a mixture thereof.
12. The powder according to any one of the preceding claims, wherein the powder further comprises a pH adjusting agent.
13. The powder according to claim 12, wherein the pH adjusting agent is an alkaline agent, optionally wherein the pH adjusting agent is selected from the group consisting of carbonates (including bicarbonates), silicates, aluminates, acetates, glycinates, phosphates, glycerophosphates, citrates, borates, hydroxides and mixtures thereof.
14. A powder according to claim 12 or claim 13, wherein the pH adjuster is present in about 1% to about 10% by weight of the powder.
15. A powder according to any preceding claim, wherein the powder is provided in the form of particles or granules.
16. A powder according to any one of the preceding claims, wherein the powder further contains a filler, a flavouring agent, a salivation agent and / or a controlled release agent.
17. A powder according to any preceding claim, wherein the powder is suitable for use in a pouch for releasing nicotine or a salt thereof when the pouch is placed in the mouth.
18. A permeable sealed bag containing a powder as defined in any one of claims 1 to 17.
19. A container containing at least 1 g of a powder as defined in any one of claims 1 to 17, preferably wherein the container contains at least 10 g of the powder.
20. A method of treating nicotine dependence, treating one or more symptoms of nicotine dependence, aiding smoking cessation or ameliorating symptoms associated with a disease or condition selected from the group consisting of dementia, Alzheimer's disease, Parkinson's disease, Huntington's disease and depression, the method comprising administering to a population in need thereof a powder as defined in any one of claims 1 to 17.
21. A powder comprising a solid porous chemically bonded ceramic system and a flavoring agent, wherein the flavoring agent is located within the pores of the chemically bonded ceramic system.
22. The powder of claim 21, wherein at least 80% by weight of the flavoring agent is located within pores in the chemically bonded ceramic system.
23. A powder according to claim 21 or claim 22, wherein the chemically bonded ceramic system is formed in the presence of the flavouring agent.
24. The powder according to any one of claims 21 to 23, wherein the chemically bonded ceramic system is based on calcium phosphate, calcium sulfate, calcium silicate, calcium aluminate or mixtures thereof.
25. The powder according to any one of claims 21 to 24, wherein the chemically bonded ceramic system is based on calcium sulfate.
26. The powder of any one of claims 21 to 25, wherein the chemically bonded ceramic system is present in about 40% to about 98% by weight of the powder.
27. A powder according to any one of claims 21 to 26, wherein the powder is provided in the form of particles or granules.
28. A powder according to any one of claims 21 to 27, wherein the powder further comprises a filler, a salivation agent and / or a controlled release agent.
29. A powder according to any one of claims 21 to 28, wherein the powder is suitable for use in a sachet for releasing the flavouring agent when the sachet is placed in the mouth.
30. The powder according to any one of claims 21 to 29, wherein the flavoring agent is selected from the group consisting of sugar, sugar alcohol and artificial sweeteners.
31. The powder according to any one of claims 21 to 29, wherein the flavoring agent is selected from the group consisting of menthol, peppermint, wintergreen, sweet mint, spearmint, vanillin, chocolate, black cherry, coffee, cinnamon, clove, tobacco, citrus, fruit flavorings and mixtures thereof.
32. The powder of any one of claims 21 to 31, wherein the flavoring agent is present in an amount between 0.1% and 50% by weight of the combination of the solid porous chemically bonded ceramic system and the flavoring agent.
33. A food product or a health product comprising the powder according to any one of claims 21 to 32.
34. An intraoral pouch comprising a powder according to any one of claims 21 to 32 and nicotine or a salt thereof.
Citation Information
Cited By
Application of combination of nicotine and second-generation antipsychotic in preparation of drug for relieving bipolar depression
CN120983432A
Pharmaceutical composition for improving bipolar depression and pharmaceutical preparation and application thereof
CN121041281A
